Carbon nanotube dispersion composition, carbon nanotube resin composition, mixture slurry, electrode film, and nonaqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2024225207
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-01
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
【0016】 本開示の実施形態の一つによれば、電池性能を改善し得るカーボンナノチューブ分散組成物、カーボンナノチューブ樹脂組成物、及び合材スラリー、並びにこれらを用いて得られる電極膜、及び非水電解質二次電池を提供することができる。
Smart Images

Figure 2025036465000001 
Figure 2025036465000002 
Figure 2025036465000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a carbon nanotube dispersion composition, a carbon nanotube resin composition, a composite slurry, an electrode film, and a nonaqueous electrolyte secondary battery. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and high capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.
[0003] Carbon materials, such as graphite, are used as the negative electrode material for these lithium-ion secondary batteries. Carbon materials have a lower potential close to that of lithium (Li) and have a large charge / discharge capacity per unit mass. However, the charge / discharge capacity per mass of these electrode materials has reached a level close to the theoretical value, and the energy density per mass of the battery is approaching its limit. Therefore, in order to increase the utilization rate of the electrode, attempts are being made to reduce the conductive additives and binders that do not contribute to the discharge capacity.
[0004] As the conductive assistant, carbon black, ketjen black, fullerene, graphene, and fine carbon fibers such as carbon nanotubes and carbon nanofibers are used. In particular, carbon nanotubes, which are a type of fine carbon fiber, are widely used. For example, by adding carbon nanotubes to a negative electrode containing graphite and silicon, the electrode resistance is reduced, the load resistance of the battery is improved, the strength of the electrode is improved, and the expansion and contraction properties of the electrode are improved, thereby improving the cycle life of a lithium ion secondary battery (see, for example, Patent Documents 1, 2, and 3). In addition, the addition of carbon nanotubes to a positive electrode to reduce the electrode resistance is also being studied (see, for example, Patent Document 4).
[0005] Patent Document 5 discloses that carbon nanotubes are specified by the pH, BET specific surface area, and average fiber length of a carbon nanotube aqueous dispersion in order to obtain an electrode film with excellent conductivity and adhesion. Patent Document 6 discloses that carbon nanotube dispersions are specified by the average outer diameter, BET specific surface area, fiber length, complex modulus, and phase angle of carbon nanotubes in order to obtain an electrode film with excellent conductivity and adhesion. Patent Document 7 discloses that multi-walled carbon nanotubes are specified by the average aspect ratio, tortuosity, secondary particle size, secondary particle size, and bulk density of inorganic oxide fine particles in order to obtain an aggregate of multi-walled carbon nanotubes with good dispersibility in resins, solvents, etc. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 4-155776 [Patent Document 2] Japanese Patent Application Publication No. 4-237971 [Patent Document 3] JP 2004-178922 A [Patent Document 4] JP 2011-70908 A [Patent Document 5] Patent No. 6961152 [Patent Document 6] Patent No. 6801806 [Patent Document 7] JP 2012-082077 A Summary of the Invention [Problem to be solved by the invention]
[0007] Patent Documents 5 and 6 disclose that a nonaqueous electrolyte secondary battery having excellent rate characteristics and cycle characteristics can be provided by obtaining an electrode film having excellent electrical conductivity and adhesion. On the other hand, it is expected that the battery performance can be further improved by specifying a more microscopic dispersion state of carbon nanotubes in the electrode film.
[0008] According to the technology disclosed in Patent Document 7, it is disclosed that a multi-walled carbon nanotube having a bent shape is preferable to one having a high linearity, since a certain degree of bending of the multi-walled carbon nanotube prevents aggregation when added to a resin, etc. On the other hand, in order to secure a conductive path between multiple particles of active material in an electrode film and improve battery performance, investigations from a different perspective are also expected.
[0009] An object of the present disclosure is to provide a carbon nanotube dispersion composition, a carbon nanotube resin composition, and a composite slurry that can improve battery performance, as well as an electrode film and a nonaqueous electrolyte secondary battery obtained using these. [Means for solving the problem]
[0010] Some of the embodiments of the present disclosure relate to the following. However, the present invention is not limited to the following and may include various embodiments.
[0011] [1] A carbon nanotube dispersion composition comprising carbon nanotubes, a dispersant, and a solvent, and satisfying the following (1) and (2): (1) The average outer diameter of the carbon nanotubes contained in the carbon nanotube dispersion composition, calculated from an SEM image of the carbon nanotubes, is 15 nm or more and 50 nm or less. (2) When the target pixel group of an SEM image of carbon nanotubes contained in a carbon nanotube dispersion composition is defined as a carbon nanotube, and linearity is defined as the distance between the two most distant points (absolute maximum length) divided by the length of the free curve (skeleton length), the percentage of carbon nanotubes with a linearity of 0.9 or more for a skeleton length of 1 μm or more is 40% or more and 90% or less.
[0012] [2] (3) In the Raman spectrum of the coating film of the carbon nanotube dispersion composition, -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 The carbon nanotube dispersion composition according to [1], wherein the G / D ratio is 1.0 to 20.0, where D is the maximum peak intensity within the range.
[0013] [3] (4) After freeze-drying the carbon nanotube dispersion composition, the powder passed through a 60 μm mesh has a BET specific surface area relative to the carbon nanotube mass of 50 to 130 m 2 / g of the carbon nanotube dispersion composition according to [1] or [2]. [4](5) The carbon nanotube dispersion composition according to any one of [1] to [3], wherein the complex modulus of elasticity at 25°C and a frequency of 10 Hz as determined by dynamic viscoelasticity measurement is 0.1 Pa or more and 200 Pa or less. [5](6) The carbon nanotube dispersion composition according to any one of [1] to [4], wherein the phase angle at 25° C. and a frequency of 10 Hz as determined by dynamic viscoelasticity measurement is 3° or more and 60° or less.
[0014] [6] A carbon nanotube resin composition comprising the carbon nanotube dispersion composition according to any one of [1] to [5] and a binder. [7] A composite slurry comprising the carbon nanotube dispersion composition according to any one of [1] to [5], a binder, and an active material.
[0015] [8] An electrode film, which is a coating film of a composite slurry, the composite slurry containing the carbon nanotube dispersion composition according to any one of [1] to [5], a binder, and an active material. [9] A nonaqueous electrolyte secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode includes the electrode film according to [8]. Effect of the Invention
[0016] According to one embodiment of the present disclosure, it is possible to provide a carbon nanotube dispersion composition, a carbon nanotube resin composition, and a composite slurry that can improve battery performance, as well as an electrode film and a nonaqueous electrolyte secondary battery obtained using these. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the carbon nanotube dispersion composition, and the resin composition, composite slurry, electrode film, and nonaqueous electrolyte secondary battery containing the carbon nanotube dispersion composition will be described in detail using several embodiments of the present disclosure. However, the present disclosure is not limited to these embodiments and various modifications are possible.
[0018] In this disclosure, carbon nanotubes may be abbreviated as "CNTs", and carbon nanotube dispersion compositions may be abbreviated as "CNT dispersion compositions". In this disclosure, SEM images refer to images captured by a scanning electron microscope. Scanning electron microscopes are also simply referred to as "SEMs".
[0019] The present inventors have found that, when the average outer diameter and linearity index of carbon nanotubes satisfy predetermined ranges in a state where the carbon nanotubes are contained in a carbon nanotube dispersion composition, one (i.e., each) carbon nanotube comes into contact with multiple particles of active material (at a higher rate) in the electrode film, improving the conductivity between the particles of the active material, thereby providing a secondary battery with excellent rate characteristics and cycle characteristics. Based on this finding, the present inventors have completed the present invention.
[0020] As an electrode material, whether it is a negative electrode or a positive electrode, multiple particles of active material are electrically connected by one carbon nanotube, thereby increasing electrical conductivity. When the carbon nanotube has linearity, one carbon nanotube can contact a larger number of particles of active material, which contributes to electrical conductivity. This means that a small amount of carbon nanotubes can be expected to contribute significantly to electrical conductivity.
[0021] For example, the packing density of the active material in the electrode film can be increased by reducing the volume of the dispersant, binder, etc., but the packing density of the active material can be further increased by reducing the amount of carbon nanotubes themselves used and thereby reducing the volume.
[0022] When a carbon-based active material is used in the negative electrode, a single carbon nanotube can electrically connect multiple particles of the carbon-based active material to increase the conductivity. However, when a silicon-based active material is used in the negative electrode, volume changes tend to occur easily due to charging and discharging. When a volume change occurs in the negative electrode, the electrical connection between the particles of the active material is cut off, and some active material particles may become electrically isolated. Even if a volume change occurs in the active material particles, the linear carbon nanotube can relatively easily maintain contact with multiple particles of the active material due to its linearity, preventing the interruption of the conductive path and suppressing a decrease in battery capacity.
[0023] Similarly, in the positive electrode, a single carbon nanotube can electrically connect multiple particles of active material to ensure a conductive path, so even a small amount of carbon nanotubes can be expected to make a significant contribution to conductivity.
[0024] <Carbon nanotube dispersion composition> One embodiment relates to a carbon nanotube dispersion composition. The carbon nanotube dispersion composition includes at least carbon nanotubes, a dispersant, and a solvent.
[0025] The carbon nanotube dispersion composition is characterized by satisfying the following (1) and (2). (1) The average outer diameter of the carbon nanotubes contained in the carbon nanotube dispersion composition, calculated from an SEM image of the carbon nanotubes, is 15 nm or more and 50 nm or less. (2) When the pixel group of the target of an SEM image of carbon nanotubes contained in a carbon nanotube dispersion composition is taken as a carbon nanotube (i.e., based on the pixelated carbon nanotubes in an SEM image of carbon nanotubes contained in a carbon nanotube dispersion composition, or in other words, the pixel group corresponding to the carbon nanotubes is taken as a proxy), and linearity is defined as the distance between the two most distant points (absolute maximum length) divided by the length of the free curve (skeleton length), the percentage of carbon nanotubes with a linearity of 0.9 or more for a skeleton length of 1 μm or more is 40% or more and 90% or less.
[0026] Hereinafter, the index specified in (2) above will also be referred to as the linearity index.
[0027] When contained in a carbon nanotube dispersion composition, the average outer diameter of the carbon nanotubes falls within a specified range and the linearity index is specified, so that a secondary battery using the carbon nanotube dispersion composition can provide excellent battery performance.
[0028] Although the reason is not bound by theory, it is believed that by satisfying condition (1) and condition (2), the linearity of the carbon nanotubes is maintained in the electrode film, and each carbon nanotube comes into contact with multiple particles of the active material at a higher rate, thereby improving the electrical conductivity. The number of particles of the active material that one carbon nanotube comes into contact with may be 2 or more, and more preferably 3 or more. It is not necessary for all carbon nanotubes to come into contact with multiple particles of the active material, and it is sufficient that only some of the carbon nanotubes come into contact with multiple particles of the active material.
[0029] In condition (1), the average outer diameter of the carbon nanotubes is preferably 15 nm or more, more preferably more than 17 nm, more preferably 19 nm or more, and even more preferably 21 nm or more. In these ranges, the carbon nanotubes are resistant to bending under stress, and can maintain the conductive paths stretched between the active materials whose volume changes with the absorption and release of lithium ions. In addition, it is difficult to obtain carbon nanotubes having an average outer diameter of less than 15 nm so as to have physical property values within the appropriate range of the present disclosure due to their manufacturing method. For example, in a carbon nanotube dispersion composition, it is difficult to synthesize and obtain a carbon nanotube raw material that has an average outer diameter of less than 15 nm and can have the linearity index of condition (2). In addition, when using a carbon nanotube raw material having an average outer diameter of 15 nm or more, a method for producing a carbon nanotube dispersion composition so that the carbon nanotube dispersion composition has the linearity index of condition (2) has not been known.
[0030] In condition (1), the average outer diameter of the carbon nanotubes is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less. In these ranges, the number of fibers per mass of the carbon nanotubes can be increased, and the number of active materials to which the carbon nanotubes are distributed can be increased, thereby further improving the battery performance. In addition, when the average outer diameter of the carbon nanotubes is in the range of 50 nm or less, the carbon nanotubes themselves have low resistance and can further increase the conductivity. This can further improve the rate characteristics of the secondary battery. Furthermore, since the carbon nanotubes of this embodiment have linearity, they have high conductivity, but also contact multiple particles of the active material in the electrode film to ensure a conductive path, which can contribute to improving the conductivity. For example, the average outer diameter of the carbon nanotubes may be 15 to 50 nm, 15 to 40 nm, or 15 to 30 nm, or 17 to 40 nm, 19 to 30 nm, or 21 to 30 nm.
[0031] In the condition (2), the linearity index of the carbon nanotubes is preferably 40% or more, more preferably 50% or more, and even more preferably 60% or more. Carbon nanotubes with a high linearity index can contact multiple particles of active material at a higher rate in the electrode film, and can contribute to high conductivity in the secondary battery.
[0032] In the condition (2), the linearity index of the carbon nanotubes is preferably 90% or less, more preferably 80% or less, and even more preferably 70% or less. When the linearity index of carbon nanotubes is high, the carbon nanotubes themselves tend to become hard, and there is a possibility that the fibers of the carbon nanotubes may be broken during the dispersion process for preparing an electrode film from the carbon nanotube dispersion composition. In this case, the number of particles of active material that can be contacted by one carbon nanotube in the electrode film decreases, and sufficient conductivity may not be obtained in the secondary battery. For example, the linearity index of the carbon nanotubes may be 40 to 90%, 50 to 90%, 60 to 90%, or may be 50 to 80%, 50 to 70%, or 60 to 70%.
[0033] In the present disclosure, the average outer diameter of the carbon nanotubes in the carbon nanotube dispersion composition is a value measured by the following procedure.
[0034] A sample is prepared using the carbon nanotube dispersion composition so that individual carbon nanotubes can be observed by SEM. From the SEM image of this sample, 300 carbon nanotubes are selected at random, and the number-average average outer diameter is determined. Specifically, the following procedure is followed.
[0035] Sample preparation: The CNT dispersion composition is diluted with a solvent so that the CNT concentration is 0.048 mass%. The solvent used is the same as that used to prepare the CNT dispersion composition. A few μL of the diluted dispersion composition is spray-coated onto a mica substrate, and then dried on a hot plate at 100°C to prepare a substrate for observing the average outer diameter of the CNTs.
[0036] Measurement method: Observe and photograph carbon nanotubes using a scanning electron microscope. Next, randomly select 300 carbon nanotubes from the photograph and measure the outer diameter of each. Next, calculate the average outer diameter (nm) of the carbon nanotubes as the number average of the outer diameters. Specifically, the average outer diameter is measured according to the measurement method in the Examples.
[0037] In the present disclosure, the linearity index of carbon nanotubes in a carbon nanotube dispersion composition is a numerical value measured by the following procedure.
[0038] A sample is prepared using the carbon nanotube dispersion composition, allowing individual carbon nanotubes to be observed by SEM. A total of 1000 to 3000 carbon nanotubes are selected from the SEM image of this sample, and the absolute maximum length and skeleton length of each carbon nanotube are measured, and the number of carbon nanotubes with a skeleton length of 1 μm or more is counted, and the linearity and linearity index are calculated. Specifically, the following procedure is followed.
[0039] Sample preparation: The CNT dispersion composition is diluted with a solvent so that the CNT concentration is 0.048 mass%. The solvent used is the same as that used to prepare the CNT dispersion composition. A few μL of the diluted dispersion composition is spray-coated onto a mica substrate, and then dried on a hot plate at 100°C to prepare a substrate for observing the CNT linearity index.
[0040] Measurement method: Obtain an SEM image of the sample substrate. At this time, set it so that the shapes of 50 to 200 carbon nanotubes can be observed in one field of view. The SEM image is taken under conditions of 4.63 nm per pixel. Note that an error range of 4.63 nm ± 10% is allowed in the shooting conditions. Move the field of view and obtain SEM images until a total of 1,000 to 3,000 carbon nanotubes can be observed.
[0041] Software: Analyze the SEM images using image analysis software such as "WinROOF2015" (Mitani Shoji Co., Ltd.), and calculate the absolute maximum length and skeleton length of each carbon nanotube. Calculate the linearity using the following formula. Linearity = absolute maximum length / skeleton length The absolute maximum length is the distance between the two most distant points among the pixels of interest (i.e., the pixels originating from that one carbon nanotube). The skeleton length is the length of the free curve made up of the target pixels.
[0042] Next, for each field of view of the SEM image, the number a of carbon nanotubes with a skeleton length of 1 μm or more is calculated, and the number b of carbon nanotubes with a skeleton length of 1 μm or more and a linearity of 0.9 or more is calculated. The linearity index is calculated using the following formula. Linearity index (%)=(b / a)×100 Specifically, the linearity index was measured according to the measurement method in the Examples.
[0043] It is more preferable that the carbon nanotube dispersion composition satisfies the following (3). (3) In the Raman spectrum of the coating film of the carbon nanotube dispersion composition, -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within this range is defined as D, the G / D ratio is 1.0 to 20.0.
[0044] The G / D ratio of the coating film of the carbon nanotube dispersion composition is preferably 1.0 or more, more preferably 1.1 or more, more preferably 1.3 or more, and even more preferably 1.7 or more. A high G / D ratio indicates high crystallinity of the carbon nanotubes. Highly crystalline carbon nanotubes have the advantage of contributing to electrical conductivity in secondary batteries. Highly crystalline carbon nanotubes tend to maintain the linearity index in the carbon nanotube dispersion composition, further increasing linearity and allowing the above-described effects to be obtained more fully.
[0045] The G / D ratio of the coating film of the carbon nanotube dispersion composition is preferably 20 or less, more preferably 10 or less, further preferably 8.0 or less, and may be 7.0 or less, 5.0 or less, or 2.0 or less. When the G / D ratio of the coating film of the carbon nanotube dispersion composition is in this range, the contact area of one carbon nanotube per one particle of the active material in the electrode film tends to be large, and the conductivity of the secondary battery can be further improved. In addition, when the crystallinity of the carbon nanotube becomes high, the carbon nanotube itself becomes hard, and the fiber length of the carbon nanotube in the carbon nanotube dispersion composition becomes short due to breakage, making it difficult to maintain the linearity index. In addition, in order to prevent breakage of the carbon nanotube, the management of the dispersion process may become complicated. From the viewpoint that the carbon nanotube itself has moderate flexibility, it is particularly preferable that the G / D ratio of the coating film of the carbon nanotube dispersion composition is 8.0 or less. For example, the G / D ratio of the coating film of the carbon nanotube dispersion composition may be 1.0 or more and 20 or less, 1.1 or more and 10 or less, or 1.3 or more and 8.0 or less, or alternatively, 1.0 or more and 7.0 or less, 1.0 or more and 5.0 or less, or 1.0 or more and 2.0 or less.
[0046] In the present disclosure, the G / D ratio of the coating film of the carbon nanotube dispersion composition is a value measured by the following procedure.
[0047] First, the carbon nanotube dispersion composition is applied to a substrate and dried to obtain a coating film. Drying may be performed at a temperature sufficient to remove volatile matter, and may be appropriately adjusted depending on the type of solvent, for example, 100°C to 200°C. The thickness of the coating film may be sufficient to allow measurement of Raman spectrum, for example, 1 to 10 μm. The Raman spectrum of the obtained coating film is measured, and the G / D ratio is calculated. In detail, the method for measuring the G / D ratio of the coating film of the carbon nanotube dispersion composition follows the measurement method in the examples.
[0048] It is more preferable that the carbon nanotube dispersion composition satisfies the following (4). (4) After freeze-drying the carbon nanotube dispersion composition, the powder passed through a 60 μm mesh has a BET specific surface area relative to the mass of carbon nanotubes of 50 to 130 m 2 / g.
[0049] The BET specific surface area of the carbon nanotube powder derived from the carbon nanotube dispersion composition relative to the carbon nanotube mass is 50m 2 / g or more is preferable, and 60m 2 / g or more is more preferable, and 65m 2 / g or more is more preferable. In these ranges, the carbon nanotubes in the carbon nanotube dispersion composition are expected to have a small average outer diameter and high electrical conductivity, which can further improve battery performance. In addition, the fiber length of the carbon nanotubes per volume is expected to be long and linearity is expected to be high, and battery performance can be further improved with a small amount of carbon nanotubes in the electrode film.
[0050] The BET specific surface area of the carbon nanotube powder derived from the carbon nanotube dispersion composition relative to the carbon nanotube mass is 130 m 2 / g or less is preferable, and 125m 2 / g or less is more preferable, and 120m 2 / g or less is more preferable. In these ranges, the carbon nanotube dispersion composition suppresses aggregation of the carbon nanotubes, and the linearity of the carbon nanotubes is maintained in the electrode film, which can further improve the battery performance. Even if the number of carbon nanotubes per volume is reduced, the carbon nanotubes have linearity, so that one carbon nanotube contacts multiple particles of the active material in the electrode film to maintain a conductive path, which can contribute to the battery performance.
[0051] By having the BET specific surface area relative to the mass of the carbon nanotubes of the carbon nanotube powder fall within these ranges, the workability of dispersing the carbon nanotube raw material in a solvent is improved, and a carbon nanotube dispersion composition with good dispersibility can be obtained. By using a carbon nanotube dispersion composition with good dispersibility, the distribution of the carbon nanotubes in the electrode film becomes more uniform, and one carbon nanotube comes into contact with a plurality of particles of more active material, ensuring a conductive path and contributing to improved battery performance.
[0052] For example, the BET specific surface area of the carbon nanotube powder derived from the carbon nanotube dispersion composition relative to the mass of the carbon nanotubes is 50 m 2 / g or more 130m 2 / g or less, 60m 2 / g or more 125m 2 / g or less, or 65m 2 / g or more 120m 2 / g or less. These ranges are preferable because they do not cause deterioration in battery performance due to excessive aggregation or overdispersion.
[0053] In the present disclosure, the BET specific surface area of the carbon nanotube powder derived from the carbon nanotube dispersion composition is a value measured by the following procedure.
[0054] 100 mL of the carbon nanotube dispersion composition is frozen in a -95°C ethanol bath for 5 hours using a freeze dryer (e.g., FDU-1200 / UT-4000 manufactured by Tokyo Rikakikai Co., Ltd.), and then dried under reduced pressure at 10 to 30 Pa for 20 hours to obtain carbon nanotube powder. The obtained carbon nanotube powder is passed through a 60 μm mesh and then the BET specific surface area is measured. In detail, the BET specific surface area of the carbon nanotube powder derived from the carbon nanotube dispersion composition is measured according to the measurement method in the Examples.
[0055] (Carbon Nanotubes) It is more preferable that the carbon nanotubes contained in the carbon nanotube dispersion composition are specified by the following characteristics. A carbon nanotube has a cylindrical shape made of planar graphite rolled up. The carbon nanotube may be either a single-walled carbon nanotube or a multi-walled carbon nanotube. A single-walled carbon nanotube has a structure in which one layer of graphite is wound. A multi-walled carbon nanotube has a structure in which two or more layers of graphite are wound. In addition, the sidewall of the carbon nanotube does not have to have a graphite structure. For example, carbon nanotubes having side walls with an amorphous structure can be used as the carbon nanotubes. From the viewpoint of suitability for industrial mass production, multi-walled carbon nanotubes are preferably used. Multi-walled carbon nanotubes are also preferred from the viewpoint of dispersion so that the average outer diameter and linearity index satisfy the desired ranges. When multi-walled carbon nanotubes are used, the carbon nanotubes may be mixed with single-walled carbon nanotubes.
[0056] The number of walls of the multi-walled carbon nanotube is preferably 3 to 30, more preferably 3 to 20, and even more preferably 3 to 10.
[0057] The shape of the carbon nanotube is not particularly limited as long as the average outer diameter and linearity index satisfy the desired range. Examples of such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stacked type), and coil-like. Among them, from the viewpoint of linearity, the shape of the carbon nanotube is preferably needle-like or cylindrical tube-like. The carbon nanotube may be a single shape or a combination of two or more shapes. When highly flexible carbon nanotubes such as fishbone-like and coil-like are included, it is sufficient that the carbon nanotubes contained in the carbon nanotube dispersion composition as a whole satisfy the average outer diameter and linearity index.
[0058] Examples of the form of carbon nanotubes include, but are not limited to, graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. Carbon nanotubes may have a single form or a combination of two or more of these forms.
[0059] In the state of being contained in the carbon nanotube dispersion composition, the average fiber length of the carbon nanotubes is preferably 1 to 5 μm, more preferably 1 to 3.5 μm. In order to measure the fiber length of the carbon nanotubes, the CNT dispersion composition is diluted with a solvent so that the CNT concentration becomes 0.048 mass%, and then the diluted dispersion composition is spray-coated on a mica substrate in an amount of several μL, and then dried on a hot plate at 100° C. to prepare a substrate for observing the CNT fiber length. The solvent used in preparing the CNT dispersion composition is used as the solvent.
[0060] The SEM image is analyzed using image analysis software such as "WinROOF2015" (manufactured by Mitani Shoji Co., Ltd.), and the skeletal length of one carbon nanotube is calculated as the fiber length. The average of the fiber lengths of 1,000 to 3,000 carbon nanotubes is taken as the average fiber length.
[0061] The maximum fiber length of the carbon nanotubes contained in the carbon nanotube dispersion composition is preferably 20 μm or less, more preferably 10 μm or less. The maximum fiber length of the carbon nanotubes can be measured by image analysis using the same method as for the evaluation of the average fiber length.
[0062] (Carbon nanotube raw material) The carbon nanotube dispersion composition can be obtained using a carbon nanotube raw material. Below, some examples of carbon nanotube raw materials that can be used in the manufacturing method of the carbon nanotube dispersion composition will be described. The carbon nanotube dispersion composition according to the embodiment can exert its effect by using carbon nanotubes obtained from various sources. In the following description, the carbon nanotube raw material means carbon nanotubes in the raw material state before being added to the carbon nanotube dispersion composition.
[0063] The average outer diameter of the carbon nanotube raw material is preferably 50 nm or less, more preferably 40 nm or less, or even more preferably 20 nm or less. Within these ranges, the amount of dispersant can be reduced relative to the carbon nanotube raw material, and the packing density of the active material in the electrode film can be increased. For example, the average outer diameter of the carbon nanotube raw material may be 1 to 50 nm, 5 to 40 nm, or 7 to 20 nm. By using the carbon nanotube raw material within this range, a carbon nanotube dispersion composition having an average outer diameter and linearity index in a more suitable range can be obtained.
[0064] The standard deviation of the outer diameter of the carbon nanotube raw material is preferably 1 to 5 nm, and more preferably 1 to 4 nm.
[0065] To measure the average outer diameter of the carbon nanotube raw material, first, observe and photograph the carbon nanotubes using a scanning electron microscope. Next, randomly select 300 carbon nanotubes from the photograph and measure the outer diameter of each. Next, calculate the average outer diameter (nm) of the carbon nanotube raw material as the number average of the outer diameters.
[0066] The linearity index of the carbon nanotube raw material may be 40 to 90%, 50 to 90%, 60 to 90%, 50 to 80%, or 60 to 70%. By using the carbon nanotube raw material in this range, it is possible to obtain a carbon nanotube dispersion composition containing carbon nanotubes that have an average outer diameter and a linearity index in a more suitable range.
[0067] The linearity index of the carbon nanotube raw material is a value determined as described above using the same procedure as for the sample taken out from the carbon nanotube dispersion composition.
[0068] The carbon nanotube raw material has a Raman spectrum of 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within this range is D, the G / D ratio may be 0.8 to 100, 1.1 to 10, or 1.7 to 7. By using a carbon nanotube raw material within these ranges, it is possible to obtain a carbon nanotube dispersion composition containing carbon nanotubes exhibiting a G / D ratio within a more suitable range.
[0069] The G / D ratio of the carbon nanotube raw material is a value determined by the same procedure as for the coating film of the carbon nanotube dispersion composition described above.
[0070] The BET specific surface area of the carbon nanotube raw material is 100 to 1000 m 2 / g, 150-800m 2 / g, or 200-500m 2 / g. By using a carbon nanotube raw material in these ranges, it is possible to obtain a carbon nanotube dispersion composition containing carbon nanotubes exhibiting a BET specific surface area in a more suitable range. The BET specific surface area of the carbon nanotube raw material is preferably within 1000 m 2 / g or less, 800m 2 / g or less, or 500m 2 / g or less is preferable, and 100m 2 / g or more, 120m 2 / g or more, or 150m 2 In these ranges, the dispersion treatment can be simplified when dispersing the carbon nanotube raw material in a solvent, and dispersibility can be obtained with a small amount of dispersant, so that the packing density of the active material in the electrode film can be increased.
[0071] The BET specific surface area of the carbon nanotube raw material is a value determined by the same procedure as for the carbon nanotube powder derived from the carbon nanotube dispersion composition described above.
[0072] The carbon nanotube raw material may be used alone or in combination of two or more. When two or more carbon nanotube raw materials are used, it is preferable that at least a part of the two or more carbon nanotube raw materials has a BET specific surface area in the above-mentioned range, and it is more preferable that all of the two or more carbon nanotube raw materials have a BET specific surface area in the above-mentioned range. In addition, when a mixed powder of all of the two or more carbon nanotube raw materials is used, it is more preferable that the mixed powder has a BET specific surface area in the above-mentioned range.
[0073] The average fiber length of the carbon nanotube raw material is preferably 1 to 5 μm, and more preferably 1 to 3.5 μm. The fiber length of the carbon nanotube raw material can be measured by dispersing the carbon nanotube raw material in toluene using an ultrasonic homogenizer, and then observing the carbon nanotubes deposited on a mica substrate with an SEM and analyzing the images. The SEM image is analyzed using image analysis software such as "WinROOF2015" (manufactured by Mitani Shoji), and the skeleton length of each carbon nanotube is calculated as the fiber length. The average fiber length is calculated by counting the fiber lengths of 1,000 to 3,000 carbon nanotubes.
[0074] The maximum fiber length of the carbon nanotube raw material is preferably 20 μm or less, more preferably 10 μm or less. The maximum fiber length of the carbon nanotube raw material can be measured by dispersing the carbon nanotube raw material in toluene using an ultrasonic homogenizer, and then depositing the carbon nanotubes on a mica substrate and observing them with a SEM and analyzing the images.
[0075] The volume resistivity of the carbon nanotube raw material is 1.0×10 -2 ~3.0×10 -2 Ω cm is preferred, and 1.0×10 -2 ~2.0×10-2 It is more preferable that the volume resistivity is Ω·cm. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (for example, Loresta GP powder resistivity measuring system "MCP-PD-51" manufactured by Mitsubishi Chemical Analytech Co., Ltd.). It is more preferable that the volume resistivity of the carbon nanotubes contained in the carbon nanotube dispersion composition satisfies the above range, similar to that of the carbon nanotube raw material.
[0076] The carbon purity of the carbon nanotube raw material is expressed as the content (%) of carbon atoms in the carbon nanotube raw material. The carbon purity is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, relative to 100% by mass of the carbon nanotube raw material. It is more preferable that the carbon purity of the carbon nanotubes contained in the carbon nanotube dispersion composition satisfies the above range, similar to that of the carbon nanotube raw material.
[0077] The amount of metal contained in the carbon nanotube raw material is preferably less than 10% by mass, more preferably less than 5% by mass, even more preferably less than 2% by mass, and even more preferably less than 1% by mass, based on 100% by mass of the carbon nanotube raw material. Examples of metals contained in the carbon nanotube raw material include metals or metal oxides used as catalysts during the synthesis of the carbon nanotube raw material. Specifically, examples include at least one metal selected from the group consisting of cobalt, nickel, aluminum, magnesium, silica, manganese, and molybdenum, its metal oxide, and a composite oxide thereof. It is more preferable that the amount of metal in the carbon nanotubes contained in the carbon nanotube dispersion composition satisfies the above range, similar to the carbon nanotube raw material.
[0078] Carbon nanotubes usually exist as secondary particles. In the carbon nanotube raw material, the shape of the secondary particles of the carbon nanotubes may be, for example, a state in which general primary particles of carbon nanotubes are intricately entangled, or may be an aggregate in which carbon nanotubes are aligned in a straight line.
[0079] In the state of being contained in the carbon nanotube dispersion composition, the shape of the secondary particles of the carbon nanotubes may maintain the shape of the carbon nanotube raw material. For example, in the state of being contained in the carbon nanotube dispersion composition, the shape of the secondary particles of the carbon nanotubes is an aggregate arranged in a straight line, so that the average outer diameter and linearity index of the carbon nanotubes can be more appropriately controlled within a predetermined range.
[0080] The carbon nanotube raw material may be a surface-treated carbon nanotube. The carbon nanotube raw material may be a carbon nanotube derivative to which a functional group such as a carboxyl group is added. The carbon nanotube raw material may be a carbon nanotube containing an organic compound, a metal atom, or a substance such as a fullerene.
[0081] The carbon nanotube raw material may be carbon nanotubes produced by any method. Generally, the carbon nanotube raw material can be produced by a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method, but is not limited to these. For example, the carbon nanotube raw material can be produced by contacting a carbon source with a catalyst in an atmosphere with an oxygen concentration of 1% by volume or less at 500 to 1000° C. The carbon source may be at least one of a hydrocarbon and an alcohol.
[0082] The raw material gas that is the carbon source of the carbon nanotube raw material can be any conventionally known raw material. For example, as the raw material gas containing carbon, hydrocarbons such as methane, ethylene, propane, butane, and acetylene, carbon monoxide, and alcohols can be used, but are not limited to these. In particular, from the viewpoint of ease of use, it is desirable to use at least one of the hydrocarbons and the alcohols as the raw material gas.
[0083] When the heat treatment temperature of the carbon nanotube raw material is increased depending on the production method, the crystallinity of the carbon nanotubes increases, and the carbon nanotubes tend to become harder. In order to ensure that the hardness of the carbon nanotubes is appropriate and that the carbon nanotubes are not broken during the dispersion treatment in the production of the carbon nanotube dispersion composition, the heat treatment temperature in the production of the carbon nanotubes may be relatively low, for example, 1000° C. or lower.
[0084] In order to obtain linearity of carbon nanotubes, a certain fiber length is required, but if the crystallinity of carbon nanotubes is further increased by high-temperature heat treatment, the tendency of carbon nanotubes to break increases. From this viewpoint, it is preferable that the heat treatment temperature in the production of carbon nanotubes is relatively low. In this case, the obtained carbon nanotube raw material may contain single-walled carbon nanotubes and multi-walled carbon nanotubes alone, or a combination of both. From the viewpoint of controlling the crystallinity and fiber length of carbon nanotubes, it is easier and more industrially advantageous to produce multi-walled carbon nanotubes.
[0085] (Dispersant) The dispersant can be used without any particular limitation as long as it can disperse and stabilize the carbon nanotubes. For example, at least one of surfactants and resin-type dispersants can be used. Surfactants are mainly classified into anionic, cationic, nonionic, and amphoteric. Depending on the characteristics required for dispersing the carbon nanotubes, a suitable type of dispersant can be used in a suitable amount. In one embodiment, it is preferable to use a resin-type dispersant.
[0086] When selecting an anionic surfactant, the type is not particularly limited.Specific examples include, but are not limited to, fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfates, alkylaryl sulfonates, alkylnaphthalenesulfonates, dialkylsulfonates, dialkylsulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylaryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphoric acid sulfonates, glycerol borate fatty acid esters, and polyoxyethylene glycerol fatty acid esters.Furthermore, specific examples include, but are not limited to, sodium dodecylbenzenesulfonate, sodium lauric acid sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate, and sodium salt of β-naphthalenesulfonic acid formalin condensates.
[0087] Examples of cationic surfactants include alkylamine salts and quaternary ammonium salts.Specific examples include, but are not limited to, stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide, and dodecyl benzyl triethyl ammonium chloride.
[0088] Amphoteric surfactants include, but are not limited to, aminocarboxylates.
[0089] Nonionic surfactants include, but are not limited to, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and alkyl allyl ethers.Specific examples include, but are not limited to, polyoxyethylene lauryl ethers, sorbitan fatty acid esters, and polyoxyethylene octylphenyl ethers.
[0090] The surfactant to be selected is not limited to a single surfactant. It is also possible to use a combination of two or more surfactants. For example, a combination of an anionic surfactant and a nonionic surfactant, or a combination of a cationic surfactant and a nonionic surfactant can be used. In this case, it is preferable that the blending amount is an appropriate blending amount for each surfactant component. As a combination, a combination of an anionic surfactant and a nonionic surfactant is preferable. The anionic surfactant preferably contains a polycarboxylate. The nonionic surfactant preferably contains polyoxyethylene phenyl ether.
[0091] Specific examples of the resin-type dispersant include cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, etc., or salts thereof), polyvinyl alcohol, polyvinyl butyral, polyvinylpyrrolidone, polyacrylonitrile, polyacrylonitrile-based polymers (copolymers of polyacrylonitrile and acrylic acid, etc.), poly(meth)acrylic acid or salts thereof, poly(meth)acrylate, nitrile rubbers (acrylonitrile butadiene rubber, hydrogenated acrylonitrile butadiene rubber, copolymers of hydrogenated nitrile rubber and hydrogenated butadiene acrylonitrile, etc.). Polymers in which other substituents have been introduced into a portion of these polymers, modified polymers, etc. may also be used. Particularly preferred are methyl cellulose, ethyl cellulose, carboxymethyl cellulose, or salts thereof, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile polymers, copolymers of acrylonitrile and acrylic acid, (meth)acrylic acid, or salts thereof, hydrogenated acrylonitrile butadiene rubber, and copolymers of hydrogenated nitrile rubber and hydrogenated butadiene acrylonitrile. The resin-type dispersant may be used alone or in combination of two or more. The weight average molecular weight (Mw) of the resin-type dispersant is preferably 5,000 to 250,000, more preferably 10,000 to 150,000.
[0092] In some embodiments, the carbon nanotube dispersion composition may further include a basic compound. The basic compound may be either an organic compound or an inorganic compound, but a basic inorganic compound is preferred because it is easy to control the stability of the dispersion system. Examples of the basic inorganic compound include inorganic bases and inorganic metal salts.
[0093] The inorganic base and inorganic metal salt are preferably a compound containing at least one of an alkali metal and an alkaline earth metal, specifically, chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, borates, etc., which contain at least one of an alkali metal and an alkaline earth metal. Among these, chlorides, hydroxides, and carbonates containing at least one of an alkali metal and an alkaline earth metal are preferred because they can easily supply cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of hydroxides of alkaline earth metals include calcium hydroxide and magnesium hydroxide. Examples of carbonates of alkali metals include lithium carbonate, lithium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, potassium carbonate, and potassium hydrogen carbonate. Examples of carbonates of alkaline earth metals include calcium carbonate and magnesium carbonate. Among these, at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, lithium carbonate, and sodium carbonate is more preferred.
[0094] In some embodiments, the carbon nanotube dispersion composition may further contain other optional components such as amine compounds, wetting agents, defoamers, surfactants, pH adjusters, wetting penetrants, antioxidants, preservatives, antifungal agents, leveling agents, and thickeners, as necessary. The carbon nanotube dispersion composition may also contain conductive materials and polymeric components other than carbon nanotubes, as long as the object of the present invention is not hindered. These optional components can be added at any timing, such as before, during, or after the dispersion treatment of the carbon nanotube dispersion composition.
[0095] In some embodiments, the carbon nanotube dispersion composition may further include a defoaming agent. Any component having a defoaming effect, such as a commercially available defoaming agent, a wetting agent, a hydrophilic organic solvent, or a water-soluble organic solvent, may be used as the defoaming agent. The defoaming agent may be used alone or in combination of two or more kinds.
[0096] Examples of the defoaming agent include alcohol-based agents such as ethanol, propanol, isopropanol, butanol, octyl alcohol, hexadecyl alcohol, acetylene alcohol, ethylene glycol monobutyl ether, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, acetylene glycol, polyoxyalkylene glycol, propylene glycol, and other glycols; fatty acid ester-based agents such as diethylene glycol laurate, glycerin monoricinoleate, alkenylsuccinic acid derivatives, sorbitol monolaurate, sorbitol trilaurate, and the like. oleate, polyoxyethylene monolaurate, polyoxyethylene sorbitol monolaurate, natural wax, etc., amide-based; polyoxyalkylene amide, acrylate polyamine, etc., phosphate-based; tributyl phosphate, sodium octyl phosphate, etc., metal soap-based; aluminum stearate, calcium oleate, etc., fat-and-oil-based; animal and vegetable oils, sesame oil, castor oil, etc., mineral oil-based; kerosene, paraffin, etc., silicone-based; dimethyl silicone oil, silicone paste, silicone emulsion, organically modified polysiloxane, fluorosilicone oil, etc.
[0097] In some embodiments, the carbon nanotube dispersion composition may further include a thickener. Examples of the thickener include polysaccharides such as carboxymethylcellulose or its salt, polyvinylidene fluoride, and derivatives thereof. Examples of commercially available products include carboxymethylcellulose #1190 (manufactured by Daicel FineChem). The thickener may be used alone or in combination of two or more.
[0098] (solvent) In some embodiments, the solvent is not particularly limited as long as the carbon nanotubes can be dispersed in the solvent. The solvent may be, for example, a mixed solvent containing one or more of water and a water-soluble organic solvent. It is preferable that the solvent contains at least water. When the solvent contains water, the content of water may be 50 parts by mass or more, 80 parts by mass or more, 90 parts by mass or more, 95 parts by mass or more, or 98 parts by mass or more relative to the total solvent (100 parts by mass), and the remainder may contain a water-soluble organic solvent. In addition, the total solvent (100 parts by mass) may be water. In addition, as an embodiment, it is preferable to include an amide-based organic solvent from the viewpoint of affinity to carbon nanotubes. When the solvent includes an amide-based organic solvent, the content of the amide-based organic solvent may be 50 parts by mass or more, 80 parts by mass or more, 90 parts by mass or more, 95 parts by mass or more, or 98 parts by mass or more relative to the entire solvent (100 parts by mass). In addition, the entire solvent (100 parts by mass) may be an amide-based organic solvent.
[0099] Examples of the water-soluble organic solvent include alcohols (methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, benzyl alcohol, etc.), polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol, hexanediol, pentanediol, glycerin, hexanetriol, thiodiglycol, etc.), polyhydric alcohol ethers (ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene ... ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, etc.), amines (ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenediamine, triethylenetetramine, tetraethylenepentamine, polyethyleneimine, pentamethyldiethylenetriamine, tetramethylpropylenediamine, etc.), amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), and others such as tetrahydrofuran, urea, and acetonitrile can be used. In particular, when used in a positive electrode composite slurry, it is preferable to use an amide organic solvent as the water-soluble organic solvent, and among them, it is preferable to include at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP) and N-ethyl-2-pyrrolidone (NEP) from the viewpoint of affinity to carbon nanotubes and solubility of the fluororesin, which is the binder resin. The water-soluble organic solvent may be used alone or in combination of two or more.
[0100] (Characteristics of carbon nanotube dispersion composition) The carbon nanotube dispersion composition may be characterized by the complex modulus, phase angle, or a combination thereof at 25° C. and a frequency of 10 Hz by dynamic viscoelasticity measurement.
[0101] The carbon nanotube dispersion composition has a complex modulus of elasticity at 25° C. and a frequency of 10 Hz as measured by dynamic viscoelasticity measurement of preferably 4 Pa or more, more preferably 10 Pa or more, even more preferably 20 Pa or more, and even more preferably 30 Pa or more. The complex modulus is preferably 250 Pa or less, more preferably 200 Pa or less, even more preferably 100 Pa or less, even more preferably 80 Pa or less, and particularly preferably 47 Pa or less. The carbon nanotube dispersion composition preferably has a complex modulus of elasticity at 25°C and a frequency of 10 Hz as measured by dynamic viscoelasticity measurement of 4 Pa or more and 250 Pa or less, and more preferably 4 Pa or more and 200 Pa or less, 10 Pa or more and 100 Pa or less, 20 Pa or more and 80 Pa or less, or 20 Pa or more and 47 Pa or less.
[0102] The carbon nanotube dispersion composition has a phase angle at 25°C and a frequency of 10 Hz as measured by dynamic viscoelasticity measurement of preferably 3° or more, more preferably 8° or more, even more preferably 12° or more, and even more preferably 16° or more. Also, the phase angle is preferably 60° or less, more preferably 45° or less, even more preferably 35° or less, and even more preferably 31° or less. The carbon nanotube dispersion composition preferably has a phase angle of 3° or more and 60° or less, more preferably 8° or more and 60° or less, more preferably 16° or more and 60° or less, or even more preferably 16° or more and 35° or less, at 25°C and a frequency of 10 Hz, in dynamic viscoelasticity measurement.
[0103] The carbon nanotube dispersion composition may have a complex modulus and a phase angle at 25° C. and a frequency of 10 Hz, which are measured by dynamic viscoelasticity measurement, that satisfy the above ranges.
[0104] The complex modulus and phase angle can be evaluated by dynamic viscoelasticity measurement. The better the dispersibility of the carbon nanotubes is and the lower the viscosity of the carbon nanotube dispersion composition, the smaller the complex modulus of the carbon nanotube dispersion composition tends to be. The phase angle means the phase shift of the stress wave when the strain applied to the carbon nanotube dispersion composition is a sine wave. If it is a pure elastic body, the sine wave will be in phase with the applied strain, and the phase angle will be 0°. On the other hand, if it is a pure viscous body, the stress wave will be 90° advanced. In a general viscoelasticity measurement sample, the phase angle will be a sine wave with a phase angle greater than 0° and smaller than 90°. If the dispersibility of the carbon nanotubes in the carbon nanotube dispersion composition is good, the phase angle will approach 90°, which is the phase angle of a pure viscous body.
[0105] When the fiber length of the carbon nanotubes in the carbon nanotube dispersion composition is long, even if the dispersion is good, the complex modulus may be high because the carbon nanotubes themselves have structural viscosity. However, the carbon nanotube dispersion composition having the complex modulus and phase angle values within the above ranges has good dispersed particle size and dispersibility of the carbon nanotubes. Therefore, it can be suitably used as a carbon nanotube dispersion composition for non-aqueous electrolyte secondary batteries.
[0106] The complex modulus and phase angle at 25° C. and a frequency of 10 Hz by dynamic viscoelasticity measurement of the carbon nanotube dispersion composition are determined according to the measurement methods used in the examples.
[0107] The cumulative particle size D50 of the carbon nanotube dispersion composition is preferably 300 to 7000 nm, and more preferably 700 to 3000 nm. The cumulative particle size D50 of the carbon nanotube dispersion composition can be measured on a volume basis using a particle size distribution meter (e.g., Partical LA-960V2, manufactured by Horiba, Ltd.).
[0108] The pH of the carbon nanotube dispersion composition may be 3 to 6. The pH of the carbon nanotube dispersion composition is preferably 4 to 6, and more preferably 4 to 5. The pH of the carbon nanotube dispersion composition can be measured using a pH meter (for example, pH METER F-52, manufactured by Horiba, Ltd.).
[0109] The viscosity of the carbon nanotube dispersion composition, measured at 25°C using a Brookfield viscometer at 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, and more preferably 10 mPa·s or more and less than 2,000 mPa·s.
[0110] In one embodiment, the carbon nanotube content in the carbon nanotube dispersion composition is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the carbon nanotube dispersion composition. Within these ranges, when preparing a composite slurry, the carbon nanotube dispersion composition can be more appropriately mixed and dispersed with the active material at a ratio such that one carbon nanotube constitutes a plurality of particles of the active material.
[0111] The content of carbon nanotubes in the carbon nanotube dispersion composition is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, further preferably 5 parts by mass or less, and may be 3 parts by mass or less, relative to 100 parts by mass of the carbon nanotube dispersion composition. In these ranges, the dispersibility of the carbon nanotube dispersion composition can be better maintained. In addition, since the dispersibility is maintained in the carbon nanotube dispersion composition, when an electrode film is provided using the composite slurry, the carbon nanotubes maintain linearity in the electrode film, the number of particles of the active material that contact one carbon nanotube increases, and the performance of the secondary battery can be further improved.
[0112] For example, the content of carbon nanotubes in the carbon nanotube dispersion composition is preferably 0.2 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 3 parts by mass, per 100 parts by mass of the carbon nanotube dispersion composition.
[0113] In one embodiment, the amount of the dispersant in the carbon nanotube dispersion composition is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, still more preferably 40 parts by mass or more, and may be 60 parts by mass or more, relative to 100 parts by mass of carbon nanotubes, from the viewpoint of dispersion stability. The amount of the dispersant in the carbon nanotube dispersion composition is preferably 300 parts by mass or less, more preferably 200 parts by mass or less, still more preferably 120 parts by mass or less, and may be 100 parts by mass or less, relative to 100 parts by mass of carbon nanotubes, from the viewpoint of dispersion stability. For example, the amount of the dispersant in the carbon nanotube dispersion composition is preferably 10 to 300 parts by mass, more preferably 40 to 200 parts by mass, still more preferably 60 to 120 parts by mass, and may be 70 to 100 parts by mass, relative to 100 parts by mass of carbon nanotubes.
[0114] In one embodiment, the non-volatile content of the carbon nanotube dispersion composition may be 80 mass % or more, 90 mass % or more, 95 mass % or more, or 98 mass % or more, based on 100 mass % of the carbon nanotubes, with the remainder being solvent. Here, the non-volatile content is the mass of a dried coating film of the carbon nanotube dispersion composition.
[0115] When the carbon nanotube dispersion composition contains components other than the carbon nanotubes, the dispersant, and the solvent, the amount of the other components in the carbon nanotube dispersion composition may be 0.1 to 10 parts by mass, 0.5 to 5 parts by mass, or 1 to 3 parts by mass relative to 100 parts by mass of the carbon nanotube dispersion composition.
[0116] When the carbon nanotube dispersion composition contains a basic compound, the amount of the basic compound in the carbon nanotube dispersion composition may be 0.01 to 1 part by mass, 0.02 to 0.5 parts by mass, or 0.04 to 0.1 parts by mass, relative to 100 parts by mass of the carbon nanotube dispersion composition. When the carbon nanotube dispersion composition contains a basic compound, the amount of the basic compound in the carbon nanotube dispersion composition may be 1 to 20 parts by mass, 2 to 10 parts by mass, or 4 to 8 parts by mass, relative to 100 parts by mass of the dispersant.
[0117] When the carbon nanotube dispersion composition contains an antifoaming agent, the amount of the antifoaming agent in the carbon nanotube dispersion composition may be 0.01 to 1 part by mass, 0.02 to 0.5 parts by mass, or 0.04 to 0.1 parts by mass, relative to 100 parts by mass of the carbon nanotube dispersion composition.
[0118] (Method of manufacturing carbon nanotube dispersion composition) The method for producing the carbon nanotube dispersion composition is not particularly limited, but can be performed by mixing the carbon nanotube raw material, the dispersant, and the solvent all at once or in portions. The carbon nanotube raw material can be the one described above. In addition, when performing a dispersion treatment after mixing, it is preferable to perform the dispersion treatment so that the carbon nanotubes have a predetermined average outer diameter and linearity index in the obtained carbon nanotube dispersion composition. The dispersing device used for the dispersion treatment is not particularly limited.
[0119] As the dispersing device, a dispersing machine which is usually used for dispersing pigments or the like can be used. For example, mixers such as a disperser, a homomixer, and a planetary mixer; homogenizers (BRANSON's "Advanced Digital Sonifer (registered trademark)" MODEL 450DA, M-Technique's "Clearmix", PRIMIX's "Filmix", Silverson's "Abramix", etc.); paint conditioner (Red Devil); colloid mills (PUC's "PUC Colloid Mill", IKA's "Colloid Mill MK"); cone mills (IKA's "Cone Mill MKO", etc.); media-type dispersers including ball mills, sand mills (Shinmaru Enterprises' "Dyno Mill", etc.), attritors, pearl mills (Eirich's "DCP Mill", etc.), and Coball mills; wet jet mills (Zenus' "Zenus PY", Sugino Machine's "Starburst", Nanomizer's "Nanomizer", etc.), M-Technique's "Clear SS-5", Nara Machine's "MICROS", etc.; and other roll mills, but are not limited to these.
[0120] In some embodiments, the dispersion treatment for preparing the carbon nanotube dispersion composition is preferably carried out using a homogenizer, a media-type disperser, a media-less disperser, or a combination thereof. The dispersion treatment using a homogenizer is preferably carried out under a high pressure of, for example, 60 to 150 MPa. When the dispersion treatment is carried out using a media-type disperser, it is preferable to use beads such as zirconia beads. The diameter of the beads used is preferably smaller than 1.25 mm, more preferably 1.0 mm or less.
[0121] In the dispersion treatment, it is preferable to use a homogenizer, and the homogenizer may be used alone or in combination with at least one of a media-type disperser and a media-less disperser. In the dispersion treatment, the dispersion treatment may be performed by a method that does not use a media-type disperser so that the carbon nanotubes are not broken by collision between the media and the carbon nanotubes. In this case, the dispersion treatment may be performed using a homogenizer alone or a combination of a homogenizer and a media-less disperser. For example, by performing wet kneading using a media-less disperser before and after the dispersion treatment using a homogenizer, the fiber length of the carbon nanotubes is maintained, and carbon nanotubes having a linearity index in a more appropriate range can be included in the dispersion composition.
[0122] Examples of commercially available homogenizers include, but are not limited to, "R-MODEL such as R5, G-MODEL such as G5" manufactured by MST Co., Ltd., "STARBURST" manufactured by Sugino Machine Co., Ltd., and "OMEGA" manufactured by Ashizawa Finetech Co., Ltd. Examples of commercially available media-less dispersers include, but are not limited to, "3L Kneader" manufactured by Inoue Seisakusho Co., Ltd., "Planetary Mixer" manufactured by Inoue Seisakusho Co., Ltd., "Plastomill" manufactured by Toyo Seiki Seisakusho Co., Ltd., "Twin-screw kneading extruder PCM30" manufactured by Ikegai Co., Ltd., and "MIXING ROLL MILL" manufactured by Inoue Seisakusho Co., Ltd.
[0123] <Carbon nanotube resin composition> According to some embodiments, a carbon nanotube resin composition is provided. The carbon nanotube resin composition includes carbon nanotubes, a dispersant, a solvent, and a binder. The carbon nanotube resin composition may include a carbon nanotube dispersion composition and a binder. The binder will be described below.
[0124] (binder) The binder is a resin that binds substances such as carbon nanotubes together.
[0125] Examples of the binder include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, and the like as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose resins such as carboxymethylcellulose; rubbers such as styrene butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene. Examples of the fluororesin include polytetrafluoroethylene. The binder may be a modified product, mixture, or copolymer of the above resins. Among these, it is preferable that the binder contains at least one selected from the group consisting of carboxymethylcellulose, styrene butadiene rubber, and polyacrylic acid.
[0126] Carboxymethyl cellulose used as a binder preferably has a high viscosity. For example, the viscosity of a 1% aqueous solution of carboxymethyl cellulose when prepared is preferably 500 to 6000 mPa·s, and more preferably 1000 to 3000 mPa·s. The viscosity of a 1% aqueous solution of carboxymethyl cellulose can be measured using a B-type viscometer rotor at a rotation speed of 60 rpm under conditions of 25°C.
[0127] The carboxymethyl cellulose used as the binder preferably has a high degree of etherification. For example, the degree of etherification is preferably 0.6 to 1.5, and more preferably 0.8 to 1.2.
[0128] The styrene-butadiene rubber used as the binder resin may be any one generally used as a binder for electrodes, so long as it is an oil-in-water emulsion. In one embodiment, the binder preferably contains an emulsion of styrene-butadiene rubber. For example, "TRD2001" manufactured by JSR Corporation can be suitably used.
[0129] The type and amount of the binder are appropriately selected according to the properties of the coexisting materials such as the carbon nanotubes and the active material. In the carbon nanotube resin composition, the content of the binder may be 1 to 100 parts by mass, 5 to 500 parts by mass, or 10 to 30 parts by mass relative to 1 part by mass of the carbon nanotubes.
[0130] The carbon nanotube resin composition contains carbon nanotubes, a dispersant, a solvent, and a binder, and can be obtained by mixing them all at once or in portions. In another example, the carbon nanotube resin composition contains a carbon nanotube dispersion composition and a binder, and can be obtained by mixing the binder with the carbon nanotube dispersion composition. In either method, it is preferable that the average outer diameter and linearity index of the carbon nanotubes in the obtained carbon nanotube resin composition satisfy the ranges described for the carbon nanotube dispersion composition.
[0131] For example, in mixing the carbon nanotube dispersion composition with the binder, the dispersion device described in the carbon nanotube dispersion composition may be used so as to prevent the carbon nanotubes from being broken by mixing, which allows the average outer diameter and linearity index of the carbon nanotubes in the carbon nanotube resin composition to be maintained within a predetermined range.
[0132] The carbon nanotube resin composition may further include additional optional components. The additional optional components may be those described in the carbon nanotube dispersion composition above.
[0133] <Compound slurry> According to some embodiments, a composite slurry is provided. The composite slurry includes carbon nanotubes, a dispersant, a solvent, a binder, and an active material. The composite slurry may include a carbon nanotube resin composition and an active material, or may include a carbon nanotube dispersion composition, a binder, and an active material. The active material is described below.
[0134] (active material) Active materials are materials that are the basis of battery reactions. From the viewpoint of electromotive force, active materials are classified into positive electrode active materials and negative electrode active materials.
[0135] The positive electrode active material is not particularly limited, but may be metal compounds such as metal oxides and metal sulfides capable of doping or intercalating lithium ions, as well as conductive polymers.
[0136] Examples of the oxides include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, and inorganic compounds such as transition metal sulfides. 2 O 5 , V 6 O 13 , and TiO 2 transition metal oxide powders such as lithium nickel oxide, lithium cobalt oxide, and lithium manganate with layered structures, lithium manganate with spinel structures, and other composite oxide powders of lithium and transition metals; lithium iron phosphate-based materials, which are phosphate compounds with olivine structures; TiS 2 and transition metal sulfide powder such as FeS.
[0137] The positive electrode active material may be an organic compound. For example, a conductive polymer such as polyaniline, polyacetylene, polypyrrole, or polythiophene may be used. The positive electrode active material may be a mixture of the inorganic compound and the organic compound.
[0138] The negative electrode active material is not particularly limited as long as it can be doped or intercalated with lithium ions. For example, alloy systems such as metallic Li, its alloy tin alloy, silicon alloy, and lead alloy, Li X Fe 2 O 3 、Li X Fe 3 O 4 、Li X WO 2 (x is a number where 0 < x < 1.), metal oxide systems such as lithium titanate, lithium vanadate, and lithium silicate, conductive polymer systems such as polyacetylene and poly-p-phenylene, amorphous carbonaceous materials such as soft carbon and hard carbon, graphiteaceous materials such as artificial graphite and natural graphite including highly graphitized carbon materials, carbon materials such as carbon black, mesophase carbon black, resin-fired carbon materials, gas-phase grown carbon fibers, and carbon fibers. These negative electrode active materials can be used alone or in combination of two or more.
[0139] In one embodiment, as the negative electrode active material, a silicon-based negative electrode active material which is a negative electrode active material containing silicon such as a silicon alloy and lithium silicate is preferable.
[0140] Examples of the silicon-based negative electrode active material include so-called metallurgical grade silicon produced by reducing silicon dioxide with carbon; industrial grade silicon with reduced impurities by treatment such as acid treatment or directional solidification of metallurgical grade silicon; high-purity silicon in different crystalline states such as single crystal, polycrystal, and amorphous produced from silane obtained by reacting silicon; silicon with adjusted crystalline state and deposition state while being made highly pure by methods such as sputtering and EB evaporation (electron beam evaporation) of industrial grade silicon.
[0141] Other examples include silicon oxide, which is a compound of silicon and oxygen, various alloys with silicon, and silicon compounds prepared by quenching the crystalline state of these, etc. Among these, a silicon-based negative electrode active material that is a mixture of silicon oxide and silicon nanoparticles having a structure in which silicon nanoparticles are dispersed in silicon oxide, and the outside of the mixture is coated with a carbon film, is preferred.
[0142] In one embodiment, the negative electrode active material may include a carbon material such as a carbonaceous material, a graphitic carbonaceous material, or a graphitic material in addition to the silicon-based negative electrode active material. For example, the carbonaceous material may be an amorphous carbonaceous material such as soft carbon or hard carbon. Examples of the graphite material include highly graphitized carbon materials such as artificial graphite and natural graphite, etc. Among these, it is preferable to use powders of graphite materials such as artificial graphite and natural graphite.
[0143] The amount of the silicon-based negative electrode active material is preferably 3 to 50 mass %, and more preferably 5 to 25 mass %, assuming that the carbon material such as artificial graphite and natural graphite is 100 mass %.
[0144] In one embodiment, the BET specific surface area of the active material is 0.1 to 10 m 2 / g is preferable, and 0.2 to 5m 2 / g is more preferable, and 0.3 to 3m 2 / g is more preferred.
[0145] In one embodiment, the average particle size of the active material is preferably within a range of 0.5 to 50 μm, and more preferably within a range of 2 to 20 μm. The "average particle size of the active material" described in the present disclosure refers to the average value of particle sizes (major axes) of the active material measured using an electron microscope.
[0146] (Method for producing composite slurry) The composite slurry can be prepared by various conventional methods. For example, a method of mixing an active material with a carbon nanotube resin composition, a method of mixing a binder and an active material together or in separate portions with a carbon nanotube dispersion composition, etc. The composite slurry may be obtained by mixing carbon nanotubes, a dispersant, a solvent, a binder, and an active material together or in separate portions.
[0147] Preferably, the composite slurry can be obtained by mixing the active material and the binder in a single batch or in separate batches with the carbon nanotube dispersion composition. In this method, the average outer diameter and linearity index of the carbon nanotubes in the carbon nanotube dispersion composition can be appropriately adjusted to be within a predetermined range, and the control of the dispersion conditions in the subsequent preparation of the composite slurry becomes easier.
[0148] In one embodiment, in order to obtain a composite slurry, it is preferable to further perform a dispersion treatment after adding an active material to the carbon nanotube dispersion composition or the carbon nanotube resin composition. The dispersion device used for the dispersion treatment is not particularly limited. The composite slurry can be prepared using the dispersion device described for the carbon nanotube dispersion composition.
[0149] In one embodiment, the amount of the active material in the composite slurry is preferably 20 to 90 parts by mass, more preferably 30 to 80 parts by mass, and further preferably 40 to 60 parts by mass, relative to 100 parts by mass of the composite slurry.
[0150] In one embodiment, the amount of carbon nanotubes in the composite slurry is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, even more preferably 0.1 to 1 part by mass, and even more preferably 0.15 to 0.5 parts by mass, relative to 100 parts by mass of the active material.
[0151] In one embodiment, the amount of the binder in the composite slurry is preferably 0.1 to 30 mass %, more preferably 0.5 to 20 mass %, even more preferably 1 to 10 mass %, and even more preferably 1.5 to 5 mass %, relative to 100 parts by mass of the active material.
[0152] The amount of binder in the composite slurry may be more appropriately controlled depending on the type of binder. For example, the amount of carboxymethyl cellulose used as the binder is preferably 0.5 to 3.0 mass% and more preferably 1.0 to 2.0 mass% when the mass of the active material is 100 parts by mass. The amount of styrene butadiene rubber used as the binder is preferably 0.5 to 3.0 mass% and more preferably 1.0 to 2.0 mass% when the mass of the active material is 100% by mass. The amount of polyacrylic acid used as the binder is preferably 1 to 25 mass% and more preferably 5 to 20 mass% when the mass of the active material is 100% by mass.
[0153] The composite slurry may further contain other additives. The other additives may be those described in the carbon nanotube dispersion composition. For example, from the viewpoint of coatability on a substrate, the composite slurry may additionally contain a thickener.
[0154] In one embodiment, the amount of solid content of the composite slurry is preferably 30 to 90 mass %, more preferably 30 to 80 mass %, and more preferably 40 to 70 mass %, based on 100 mass % of the composite slurry. Here, the solid content of the composite slurry is a component that can form a coating film without volatilizing in the solvent removal step.
[0155] <Electrode film> According to some embodiments, an electrode film is provided. The electrode film can be used in a secondary battery, such as a lithium ion secondary battery. For example, the electrode film can be provided as an electrode mixture layer provided on a current collector in a secondary battery. The electrode film can be obtained by forming a mixture slurry into a film. For example, the electrode film can be a coating film obtained by coating and drying the mixture slurry on a current collector.
[0156] The collector on which the electrode film is provided is not particularly limited. It may be of a material and shape applicable to various secondary batteries, and can be appropriately selected. For example, the material of the collector may be metals such as aluminum, copper, nickel, titanium, and stainless steel, and alloys thereof. The shape of the collector may generally be a flat foil, but a collector with a roughened surface, a perforated foil, or a mesh may also be used.
[0157] The method for applying the composite slurry onto the current collector is not particularly limited, and any known method can be used, such as die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. As the drying method, there can be used, for example, standing to dry, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, etc., but the drying method is not particularly limited to these.
[0158] After coating, the coating may be subjected to rolling treatment using a lithographic press and a calendar roll, etc. The thickness of the electrode film is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.
[0159] <Nonaqueous electrolyte secondary battery> According to some embodiments, a non-aqueous electrolyte secondary battery is provided. The non-aqueous electrolyte secondary battery may specifically be a lithium ion secondary battery. The non-aqueous electrolyte secondary battery includes a positive electrode, a negative electrode, and an electrolyte. In the secondary battery, at least one of the positive electrode and the negative electrode includes an electrode film, and the electrode film may be an electrode film according to an embodiment. The electrode film according to an embodiment may be a coating film of a composite slurry according to an embodiment, or may be an electrode film obtained using a carbon nanotube dispersion composition or a carbon nanotube resin composition according to an embodiment.
[0160] Either or both of the positive electrode and the negative electrode may include an electrode film according to an embodiment. In addition, the negative electrode may include an electrode film according to an embodiment, which may contribute to the improvement of rate characteristics and cycle characteristics. For example, when the negative electrode includes a silicon-based active material, the cycle characteristics tend to decrease due to volume change caused by charging and discharging. However, by using the electrode film according to an embodiment, the conductivity between particles of the active material can be maintained even before and after the volume change, and the decrease in cycle characteristics can be suppressed.
[0161] The positive electrode can be prepared by coating a composite slurry containing a positive electrode active material on a current collector and drying the coated composite slurry to form an electrode film.
[0162] The negative electrode may be prepared by coating a composite slurry containing a negative electrode active material on a current collector and drying the coated composite slurry to form an electrode film.
[0163] As the electrolyte, various conventionally known compounds capable of moving ions can be used. Examples of compounds that can be used as the electrolyte include LiBF 4 , LiClO 4 , LiPF 6 , LiAsF 6 , LiSbF 6 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3, Li(CF 3 SO 2 ) 3 C, LiI, LiBr, LiCl, LiAlCl, LiHF 2 , LiSCN, or LiBPh 4 (wherein Ph is a phenyl group). However, the electrolyte is not limited thereto, and compounds containing sodium salts and calcium salts can also be used. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.
[0164] The non-aqueous solvent is not particularly limited. For example, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0165] In one embodiment, the secondary battery preferably includes a separator. The separator may be made of, for example, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, or a material obtained by subjecting these to a hydrophilic treatment, but is not limited thereto.
[0166] The secondary battery may have various shapes, such as a paper type, a cylindrical type, a button type, and a laminated type, depending on the purpose of use.
[0167] <Another embodiment> According to some embodiments, a method for producing a carbon nanotube dispersion composition using carbon nanotubes can be provided. More specifically, a method for producing a carbon nanotube dispersion composition for use as an electrode material for a secondary battery using carbon nanotubes can be provided. For example, a method for producing a carbon nanotube dispersion composition for use in a non-aqueous electrolyte secondary battery, more specifically, in a negative electrode of a lithium ion secondary battery, more specifically, in a negative electrode containing a silicon-based active material can be provided. The carbon nanotubes used in this production method may be the carbon nanotube raw material described in the carbon nanotube dispersion composition. For example, the carbon nanotubes may at least satisfy the average outer diameter and linearity index within the ranges described above for the carbon nanotube raw material, and may optionally further satisfy one or both of the BET specific surface area and G / D ratio, and may further optionally satisfy other physical properties.
[0168] According to some embodiments, it is possible to provide a method for producing a carbon nanotube resin composition using carbon nanotubes, a method for producing a composite slurry using carbon nanotubes, a method for producing an electrode film using carbon nanotubes, and a method for producing a secondary battery using carbon nanotubes. The carbon nanotubes are as described above.
[0169] Further, according to some embodiments, a carbon nanotube dispersion composition, a carbon nanotube resin composition, a composite slurry, an electrode film, and a use of carbon nanotubes for use in a secondary battery can be provided. The carbon nanotubes are as described above. These may be various methods of using carbon nanotubes for use in a non-aqueous electrolyte secondary battery, more specifically, in a negative electrode of a lithium ion secondary battery, more specifically, in a negative electrode containing a silicon-based active material.
[0170] According to these embodiments, it is possible to include carbon nanotubes having an average outer diameter and a linearity index that satisfy a predetermined range in one or both of the positive electrode and the negative electrode in the electrode film, thereby improving the rate characteristics and cycle characteristics of the secondary battery. EXAMPLES
[0171] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "carbon nanotubes" may be abbreviated as "CNT." Unless otherwise specified, "parts" refers to "parts by mass" and "%" refers to "% by mass."
[0172] Table 1 shows the formulations and evaluation results of the CNT dispersion compositions. Table 2 shows the formulations of the composite slurry for the negative electrode. Table 3 shows the formulations of the composite slurry for the positive electrode. Tables 4 and 5 show the rate characteristics and cycle characteristics of secondary batteries using the negative and positive electrodes produced in the examples and comparative examples, respectively. Tables 2 and 3 show the mass % of each component per 100 mass % of the nonvolatile content, as well as the mass % of the total amount of nonvolatile content per 100 mass % of the composite slurry.
[0173] <1> Measurement methods for physical properties The methods for measuring physical properties used in the examples are described below.
[0174] (1) Average outer diameter of CNTs The average outer diameter of the CNT dispersion composition was measured by preparing a sample as described below using the CNT dispersion composition shown in Table 1, and using this sample, the average outer diameter was measured as described below.
[0175] Sample preparation: The CNT dispersion composition was diluted with a solvent so that the CNT concentration was 0.048% by mass. A few μL of the diluted dispersion composition was spray-coated onto a mica substrate and then dried on a hot plate at 100°C to prepare a substrate for observing the average outer diameter of the CNTs. The surface of the substrate was then sputtered with platinum. The solvent used was the same as that used to prepare the CNT dispersion composition.
[0176] Measurement method: Carbon nanotubes were observed and photographed using a scanning electron microscope (manufactured by JEOL Ltd.). Next, observations were performed at a magnification of 50,000 times, and 300 carbon nanotubes were randomly selected from multiple observation photographs, and the outer diameter of each was measured. Next, the average outer diameter (nm) of the carbon nanotubes was calculated as the number average of the outer diameters.
[0177] (2) Linearity index The linearity index of the CNT dispersion composition was measured by preparing a sample as follows using the CNT dispersion composition shown in Table 1, and using this sample, the linearity index was measured as follows.
[0178] Sample preparation: The CNT dispersion composition was diluted with a solvent so that the CNT concentration was 0.048% by mass. The diluted dispersion composition was spray-coated on a mica substrate in an amount of several μL, and then dried on a hot plate at 100° C. to prepare a substrate for observing the CNT fiber length. The surface of the substrate was then sputtered with platinum. The solvent used was the same as that used to prepare the CNT dispersion composition.
[0179] Measurement method: SEM images of the sample pieces were obtained using a scanning electron microscope (manufactured by JEOL Ltd.). At this time, the microscope was set so that the shapes of 50 to 200 carbon nanotubes could be observed in one field of view. SEM images were taken under conditions of 4.63 nm per pixel. Note that an error range of 4.63 nm ± 10% was allowed in the photographing conditions. SEM images were taken by moving the field of view until a total of 1,000 to 3,000 carbon nanotubes could be observed.
[0180] Software: SEM images were analyzed using the image analysis software "WinROOF2015" (Mitani Shoji Co., Ltd.), and the absolute maximum length and skeleton length of each carbon nanotube were calculated. Linearity was calculated using the following formula. Linearity = absolute maximum length / skeleton length The absolute maximum length is the distance between the two most distant points in the group of pixels of interest. The skeleton length is the length of the free curve made up of the target pixels.
[0181] Next, for each field of view of the SEM image, the number a of carbon nanotubes with a skeleton length of 1 μm or more was calculated, and the number b of carbon nanotubes with a skeleton length of 1 μm or more and a linearity of 0.9 or more was calculated. The linearity index was calculated using the following formula. Linearity index (%)=(b / a)×100
[0182] (3)G / D ratio The G / D ratio of the CNT dispersion composition was measured by preparing a sample as follows using the CNT dispersion composition shown in Table 1, and using this sample, the G / D ratio was measured as follows.
[0183] Sample preparation: The carbon nanotube dispersion composition was applied to a glass substrate (thickness 2 mm) using a K CONTROL COATER (No. 150) manufactured by KR PRINTCOAT, and dried to obtain a coating film. Drying was performed by leaving the substrate to stand for 5 minutes in an oven (SPHH-201 manufactured by ESPEC CORP.) at 120°C.
[0184] Measurement method: CNTs were placed in a Raman microscope (XploRA, manufactured by Horiba, Ltd.) and measurements were performed using a laser wavelength of 532 nm. The measurement conditions were: acquisition time 60 seconds, number of integrations 2, neutral density filter 10%, objective lens magnification 20 times, confocus hole 500, slit width 100 μm, measurement wavelength 100 to 3000 cm -1 The peak obtained was 1560-1600 cm -1 The maximum peak intensity in the range of G, 1310~1350cm -1 The maximum peak intensity within this range was taken as D, and the G / D ratio was calculated to be the G / D ratio of the CNT.
[0185] (4) BET specific surface area The BET specific surface area of the CNT dispersion composition was measured by preparing a sample as follows using the CNT dispersion composition shown in Table 1, and using this sample, the BET specific surface area was measured as follows. Sample preparation: 100 mL of the carbon nanotube dispersion composition was measured out into a 500 mL eggplant flask, frozen in a -95°C ethanol bath for 5 hours using a freeze dryer (Tokyo Rikakikai Co., Ltd., FDU-1200 / UT-4000) and then dried under reduced pressure at 10 to 30 Pa for 20 hours to obtain carbon nanotube powder. The obtained carbon nanotube powder was then passed through a 60 μm mesh.
[0186] Measurement method: 0.03 g of CNT was weighed using an electronic balance (MSA225S100DI, manufactured by Sartorius), and then dried at 110°C for 15 minutes while degassing. The BET specific surface area of the carbon nanotube powder was then measured using a fully automatic specific surface area measuring device (HM-model1208, manufactured by MOUNTECH). The mass used as the denominator for calculating the specific surface area was the mass of the carbon nanotubes.
[0187] (5) Complex modulus The complex modulus of the CNT dispersion composition was evaluated by performing dynamic viscoelasticity measurements using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone diameter of 35 mm and an angle of 2° at 25°C, a frequency of 10 Hz, and a strain rate range of 0.01% to 5%.
[0188] (6) Phase angle The phase angle of the CNT dispersion composition was evaluated by performing dynamic viscoelasticity measurements at 25°C, a frequency of 10 Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone diameter of 35 mm and an angle of 2°.
[0189] <Preparation of standard positive electrode> The standard positive electrodes used in the examples and comparative examples described below were prepared by the following method.
[0190] First, 68.8 parts by mass of a positive electrode active material (manufactured by BASF Toda Battery Materials LLC, HED® NCM-111 1100), 3.0 parts by mass of acetylene black (manufactured by Denka Co., Ltd., Denka Black® HS100), and 2.2 parts by mass of PVdF (polyvinylidene fluoride, manufactured by Kureha Battery Materials Japan Co., Ltd., Kureha KF Polymer W#1300) were added to a 150 cm 3 After adding the mixture to a plastic container, the mixture was mixed with a spatula until the powder was uniform. Then, 15.2 parts by mass of NMP was added, and the mixture was stirred with a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310) at 2000 rpm for 30 seconds. Then, the mixture in the plastic container was mixed with a spatula until it was uniform, and the mixture was stirred with the centrifugal mixer at 2000 rpm for 30 seconds. Then, 10.8 parts by mass of NMP was added, and the mixture was stirred with the centrifugal mixer at 2000 rpm for 30 seconds. Finally, the mixture was stirred with a high-speed stirrer at 3000 rpm for 10 minutes to obtain a positive electrode composite slurry.
[0191] Next, the positive electrode composite slurry was applied to an aluminum foil having a thickness of 20 μm as a current collector using an applicator to form a coating film. The coating film was then dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain a coating weight per unit area of the electrode of 20 mg / cm. 2 Further, a rolling process was performed using a roll press (3 ton hydraulic roll press, manufactured by Thank Metal Co., Ltd.) to adjust the density of the electrode film (dried coating film) to 3.1 g / cm. 3 A standard positive electrode was prepared.
[0192] <Preparation of standard negative electrode> The standard negative electrodes used in the examples and comparative examples described below were prepared by the following method.
[0193] A 150-mL plastic container was charged with 0.3 parts by mass of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka Company), 0.5% by mass of CMC (carboxymethyl cellulose #1190, manufactured by Daicel FineChem Corporation, non-volatile content 100%), and 47.9 parts by mass of water, and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky Corporation's Awatori Rentaro, ARE-310). Further, 44.6 parts by mass of artificial graphite (CGB-20, manufactured by Nippon Graphite Industries Co., Ltd., non-volatile content 100%) and 5.1 parts by mass of silicon (silicon monoxide, manufactured by Osaka Titanium Technologies Co., Ltd., SILICON MONOOXIDE SiO 1.3C 5μm, non-volatile content 100%) were added as active materials, and the mixture was stirred at 2,000 rpm for 150 seconds using a rotation-revolution mixer (Thinky Corporation's Awatori Rentaro, ARE-310). Next, 1.6 parts by mass of SBR (TRD2001, manufactured by JSR) was added, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation-revolution mixer (Thinky Corporation's Awatori Rentaro, ARE-310) to obtain a standard negative electrode composite material composition. The non-volatile content of the standard negative electrode composite material composition was 50% by mass.
[0194] <2> About the ingredients Details of the components used in the examples and comparative examples are shown below. MIRALON: Manufactured by HUNTSMAN, multilayer CNT CNT(A): CNT(A) synthesized by the following synthesis method, multi-walled CNT JENOTUBE 10B: JENOTUBE 10B (manufactured by JEIO, multilayer CNT) NTF01: NTF01 (Hamamatsu Carbonix, multi-walled CNT)
[0195] Dispersant 1: A dispersant synthesized by the following synthesis method Dispersant 2: A dispersant prepared by the following method Na 2 CO 3 : Fujifilm Wako Pure Chemical Industries, Ltd. NaOH: Tokyo Chemical Industry Co., Ltd., purity >98.0% CMC: Carboxymethyl cellulose #1190 (manufactured by Daicel FineChem) Styrene-butadiene rubber: TRD2001 (manufactured by JSR Corporation) HNBR: Therban3406 (hydrogenated nitrile rubber manufactured by Arlanxeo) PVdF: Solef5130 (polyvinylidene fluoride resin manufactured by Solvay) Polytetrafluoroethylene: Polyflon PTFE D-210C (manufactured by Daikin Industries, Ltd.)
[0196] <Synthesis of CNT(A)> The synthesis method of CNT(A) will be described below. A catalyst composed of iron nitrate was vapor-deposited on a silicon wafer (substrate) to form a catalyst layer composed of a metal catalyst on the surface of the substrate. Then, the catalyst-supported silicon wafer was placed in the center of a horizontal reaction tube with an internal volume of 10 L that could be pressurized and heated with an external heater. While injecting nitrogen gas, exhaust was carried out to replace the air in the reaction tube with nitrogen gas, and the atmosphere in the horizontal reaction tube was made to have an oxygen concentration of 1% by volume or less. Next, it was heated with an external heater until the central temperature in the horizontal reaction tube reached 680°C. After reaching 680°C, acetylene gas was introduced into the reaction tube at a flow rate of 2 L per minute as a carbon source, and a contact reaction was carried out for 15 hours. After the reaction was completed, the gas in the reaction tube was replaced with nitrogen gas, and the gas in the reaction tube was replaced with nitrogen gas. The temperature of the reaction tube was cooled to 100°C or less and taken out to obtain CNT(A).
[0197] <Synthesis of Dispersant 1> To a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 137 parts of ion-exchanged water, 100 parts of acrylic acid, 0.8 part of 3-mercapto-1,2-propanediol, and 0.5 part of V-50 (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, it was cooled to end the reaction. Then, unreacted raw materials were reduced by heating under reduced pressure to obtain an aqueous solution of the polymer. 500 parts of methyl ethyl ketone and 500 parts of methanol were charged into a four-neck separable flask and rotated 1,000 times with a disper. Then, the aqueous polymer solution was dropped in over 1 hour. The generated white precipitate was taken out by filtration and dried under reduced pressure to obtain Dispersant 1.
[0198] <Preparation of Dispersant 2 Solution> Capacity 1000cm 3 Into the plastic container, 475 parts by mass of NMP and 25 parts by mass of NaOH (Tosoh Corporation, Toso Pearl) were added, and the mixture was dispersed at a speed of 9000 rpm using a high-shear mixer (L5M-A, Silverson) equipped with a fine emulsion screen until the entire mixture was uniform. The mixture was then passed through a nylon filter with a mesh size of 150 μm using a filter bell to prepare a NaOH dispersion. 780 parts by mass of NMP was charged into a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, and the atmosphere was replaced with nitrogen gas. The reaction vessel was then heated to 80°C, 200 parts by mass of HNBR (Therban 3406) was added, and the mixture was stirred until the HNBR was completely dissolved. Then, 20 parts by mass of NaOH dispersion was added, and the mixture was stirred while adding air, and the reaction vessel was heated while maintaining it at 80°C for 12 hours, to obtain a dispersant 2 solution (solid concentration 20.1% by mass).
[0199] <4> CNT dispersion composition (Example 1-1) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 25 passes to obtain a dispersion composition 1.
[0200] (Example 1-2) The carbon nanotubes were changed to CNT(A), and dispersion was carried out in the same manner as in Example 1, to obtain Dispersion Composition 2.
[0201] (Examples 1-3) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container and stirred with a disperser until uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, Silverson), and the mixture was stirred at a speed of 7,000 rpm until uniform. 80 g of the dispersion liquid and 120 g of zirconia beads (bead diameter 1 mmΦ) were charged in a glass bottle (M-225, Kashiwayo Glass Co., Ltd.), and dispersion treatment was performed for 5 hours using a paint conditioner manufactured by Red Devil. After that, the dispersion liquid from which the zirconia beads had been separated was supplied to a high-pressure homogenizer (Starburst Lab HJP-17007, Sugino Machine), and a circulation type dispersion treatment was performed. The dispersion treatment was carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 20 passes to obtain Dispersion Composition 3.
[0202] (Examples 1 to 4) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, for 20 passes. Next, 80 g of the dispersion liquid and 120 g of zirconia beads (bead diameter 1 mmΦ) were placed in a glass bottle (M-225, manufactured by Kashiwa Glass Co., Ltd.), and a dispersion treatment was carried out for 5 hours using a paint conditioner manufactured by Red Devil Co., Ltd., after which the zirconia beads were separated to obtain Dispersion Composition 4.
[0203] (Examples 1 to 5) 14.4 parts by mass of dispersant 1, 16 parts by mass of MIRALON, and 69.6 parts by mass of ion-exchanged water were charged into a Labo Plastomill (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and dispersed for 3 hours, then transferred to a stainless steel container, 2565.6 parts by mass of ion-exchanged water and 1.07 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to a high shear mixer (L5M-A, manufactured by SILVERSON) and stirred at a speed of 7,000 rpm until uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through piping, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 25 passes to obtain a dispersion composition 5.
[0204] (Examples 1 to 6) 14.4 parts by mass of dispersant 1, 16 parts by mass of MIRALON, and 69.6 parts by mass of ion-exchanged water were charged into a Labo Plastomill (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and dispersed for 3 hours, then transferred to a stainless steel container, 2565.6 parts by mass of ion-exchanged water and 1.07 parts by mass of sodium carbonate were added, and a high shear mixer (L5M-A, manufactured by Silverson) was equipped with a standard square hole head and stirred at a speed of 7,000 rpm until uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through piping, and a circulation type dispersion process was performed. The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 20 passes. Next, 80 g of the dispersion liquid and 120 g of zirconia beads (bead diameter 1 mmΦ) were placed in a glass bottle (M-225, manufactured by Kashiwa Glass Co., Ltd.), and a dispersion treatment was carried out for 5 hours using a paint conditioner manufactured by Red Devil Co., Ltd., and then the zirconia beads were separated to obtain dispersion composition 6.
[0205] (Examples 1 to 7) 14.4 parts by mass of dispersant 1, 16 parts by mass of MIRALON, and 69.6 parts by mass of ion-exchanged water were charged into a Labo Plastomill (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and dispersed for 3 hours, then transferred to a stainless steel container, 2565.6 parts by mass of ion-exchanged water and 1.07 parts by mass of sodium carbonate were added, and a high shear mixer (L5M-A, manufactured by Silverson) was fitted with a standard square hole head and stirred at a speed of 7,000 rpm until uniform. Next, 80 g of the liquid to be dispersed and 120 g of zirconia beads (bead diameter 1 mmΦ) were charged into a glass bottle (M-225, manufactured by Kashiwa Glass Co., Ltd.), and dispersion treatment was performed for 5 hours using a paint conditioner manufactured by Red Devil Co., Ltd., after which the zirconia beads were separated. The liquid to be dispersed was supplied to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine Co., Ltd.) and a circulation type dispersion treatment was performed. The dispersion treatment was carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 20 passes to obtain Dispersion Composition 7.
[0206] (Examples 1 to 8) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of CNT (A) and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole type head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 40 passes to obtain a dispersion composition 8.
[0207] (Examples 1 to 9) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 20 passes to obtain a dispersion composition 9.
[0208] (Examples 1 to 10) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and 40 passes were performed to obtain a dispersion composition 10.
[0209] (Examples 1 to 11) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and 15 passes were performed to obtain a dispersion composition 11.
[0210] (Examples 1 to 12) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 55 passes to obtain a dispersion composition 12.
[0211] (Comparative Example 1-1) The carbon nanotubes were changed to JENOTUBE 10B, and dispersion was performed in the same manner as in Example 1 to obtain a comparative dispersion composition 1. However, the material ratio was 2.5 parts by mass of JENOTUBE 10B, 96.3 parts by mass of ion-exchanged water, 1.0 part by mass of dispersant 1, and 0.13 part by mass of sodium carbonate.
[0212] (Comparative Example 1-2) The carbon nanotubes were changed to NTF01, and dispersion was carried out in the same manner as in Example 1, to obtain a comparative dispersion composition 2.
[0213] (Comparative Example 1-3) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and a comparative dispersion composition 3 was obtained by performing 5 passes.
[0214] (Comparative Examples 1-4) 98.82 parts by mass of ion-exchanged water and 0.54 parts by mass of dispersant 1 were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.6 parts by mass of MIRALON and 0.04 parts by mass of sodium carbonate were added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 80 passes to obtain a comparative dispersion composition 4.
[0215] (Examples 1-101) 96.40 parts by mass of N-methyl-2-pyrrolidone (NMP) and 3.0 parts by mass of dispersant 2 solution (0.60 parts by mass of HNBR, 0.03 parts by mass of NaOH, 2.37 parts by mass of NMP) were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON was added, and a standard square-hole type head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 25 passes to obtain a dispersion composition 101.
[0216] (Examples 1-102) 96.40 parts by mass of N-methyl-2-pyrrolidone (NMP) and 3.0 parts by mass of dispersant 2 solution were added to a stainless steel container and stirred with a disperser until uniform. Then, while stirring with a disperser, 0.60 parts by mass of CNT (A) was added, and a standard square-hole type head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 25 passes to obtain a dispersion composition 102.
[0217] (Examples 1-103) 96.40 parts by mass of N-methyl-2-pyrrolidone (NMP) and 3.0 parts by mass of dispersant 2 solution were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON was added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and 15 passes were performed to obtain a dispersion composition 103.
[0218] (Examples 1-104) 96.40 parts by mass of N-methyl-2-pyrrolidone (NMP) and 3.0 parts by mass of dispersant 2 solution were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON was added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 55 passes to obtain a dispersion composition 104.
[0219] (Comparative Example 1-101) 96.40 parts by mass of N-methyl-2-pyrrolidone (NMP) and 3.0 parts by mass of dispersant 2 solution (0.60 parts by mass of HNBR, 0.03 parts by mass of NaOH, 2.37 parts by mass of NMP) were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON was added, and a standard square-hole type head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 5 passes to obtain a comparative dispersion composition 101.
[0220] (Comparative Example 1-102) 96.40 parts by mass of N-methyl-2-pyrrolidone (NMP) and 3.0 parts by mass of dispersant 2 solution were added to a stainless steel container, and the mixture was stirred with a disperser until it was uniform. Then, while stirring with a disperser, 0.60 parts by mass of MIRALON was added, and a standard square-hole head was attached to the disperser and high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was stirred at a speed of 7,000 rpm until it was uniform. The liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa for 80 passes to obtain a comparative dispersion composition 102.
[0221] <5> Preparation of CNT resin composition and composite slurry (Negative electrode composite slurry 1) Capacity 150cm 3Into a plastic container, 5.7 parts by mass of dispersion composition 1, 11.4 parts by mass of an aqueous solution in which 2% by mass of carboxymethylcellulose (manufactured by Daicel FineChem Co., Ltd., #1190, referred to as CMC in the table (hereinafter the same)) was dissolved, and 10.7 parts by mass of ion-exchanged water were weighed. Then, these were stirred for 30 seconds at 2000 rpm using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Next, 2.2 parts by mass of silicon monoxide (manufactured by Osaka Titanium Technologies Co., Ltd., SILICON MONOOXIDE, SiO 1.3C 5μm) were added, and the mixture was stirred for 5 minutes at 2000 rpm using the centrifugal mixer. Furthermore, 19.9 parts by mass of artificial graphite (manufactured by Nippon Graphite Industries Co., Ltd., CGB-20) were added, and the mixture was stirred for 10 minutes at 2000 rpm using the centrifugal mixer. Thereafter, 0.7 parts by mass of styrene-butadiene rubber (manufactured by JSR Corporation, TRD2001, non-volatile content 48%, referred to as SBR in the table (hereinafter the same)) was added, and the mixture was stirred at 2000 rpm for 30 seconds using the centrifugal mixer to obtain negative electrode composite slurry 1 having the non-volatile content by mass % shown in Table 2.
[0222] (Negative electrode composite slurry 2 to 7) Dispersion composition 1 was changed to dispersion compositions 2 to 7, and negative electrode mixture slurries 2 to 7 were obtained in the same manner as for negative electrode mixture slurry 1, respectively.
[0223] (Comparative negative electrode composite slurry 1) The same procedure as for the negative electrode composite slurry 1 was used, but the material ratios were changed to 4.5 parts by mass of the comparative dispersion composition 1, 11.3 parts by mass of an aqueous solution in which 2% by mass of carboxymethylcellulose (manufactured by Daicel FineChem Co., Ltd., #1190) was dissolved, 11.8 parts by mass of ion-exchanged water, 2.2 parts by mass of silicon monoxide (manufactured by Osaka Titanium Technologies Co., Ltd., SILICON MONOOXIDE, SiO 1.3C 5 μm), 19.6 parts by mass of artificial graphite (manufactured by Nippon Graphite Industry Co., Ltd., CGB-20), and 0.7 parts by mass of styrene butadiene rubber (manufactured by JSR Corporation, TRD2001), to obtain a comparative negative electrode composite slurry 1.
[0224] (Comparative negative electrode composite slurry 2) The same procedure as for the negative electrode composite slurry 1 was used, but the material ratios were changed to 11.4 parts by mass of the comparative dispersion composition 2, 11.4 parts by mass of an aqueous solution in which 2% by mass of carboxymethylcellulose (manufactured by Daicel FineChem Co., Ltd., #1190) was dissolved, 11.8 parts by mass of ion-exchanged water, 2.2 parts by mass of silicon monoxide (manufactured by Osaka Titanium Technologies Co., Ltd., SILICON MONOOXIDE, SiO 1.3C 5 μm), 19.9 parts by mass of artificial graphite (manufactured by Nippon Graphite Industry Co., Ltd., CGB-20), and 0.7 parts by mass of styrene butadiene rubber (manufactured by JSR Corporation, TRD2001), to obtain a comparative negative electrode composite slurry 2.
[0225] (Negative electrode composite slurry 8-12) Dispersion composition 1 was changed to dispersion compositions 8 to 12, and negative electrode mixture slurries 8 to 12 were obtained in the same manner as for negative electrode mixture slurry 1, respectively.
[0226] (Comparative negative electrode composite slurries 3-4) Comparative dispersion composition 1 was changed to comparative dispersion compositions 3 to 4, and comparative negative electrode mixture slurries 3 to 4 were obtained in the same manner as in the preparation of comparative negative electrode mixture slurry 1, respectively.
[0227] (Positive electrode composite slurry 1) Capacity 150cm 38.2 parts by mass of Dispersion Composition 1, 0.3 parts by mass of carboxymethyl cellulose (manufactured by Daicel FineChem Corporation, #1190), and 9.3 parts by mass of ion-exchanged water were weighed into a plastic container, and stirred at 2,000 rpm for 30 seconds using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Thereafter, 32.0 parts by mass of LFP (LFP-400 (manufactured by BASF, non-volatile content 100%) was added as a positive electrode active material, and the mixture was stirred for 5 minutes at 2,000 rpm using a planetary centrifugal mixer (Thinky Corporation's Awatori Rentaro, ARE-310). Further, 0.8 parts by mass of polytetrafluoroethylene (manufactured by Daikin Industries, Ltd., Polyflon PTFE D-210C, non-volatile content 60%, referred to as PTFE in the table (the same applies below)) was added, and the mixture was stirred for 30 seconds at 2,000 rpm using a planetary centrifugal mixer (Thinky Corporation's Awatori Rentaro, ARE-310) to obtain positive electrode composite slurry 1 having the non-volatile content mass % shown in Table 3.
[0228] (Positive electrode composite slurry 2-7) The dispersion composition was changed to 2 to 7, and positive electrode mixture slurries 2 to 7 were obtained in the same manner as in the positive electrode mixture slurry 1.
[0229] (Comparative positive electrode composite slurry 1) The same procedure as for the positive electrode composite slurry 1 was repeated, but the material ratios were changed to 6.5 parts by mass of the comparative dispersion composition 1, 0.3 parts by mass of carboxymethyl cellulose (manufactured by Daicel FineChem Corporation, #1190), 11.0 parts by mass of ion-exchanged water, 31.4 parts by mass of LFP (LFP-400 (manufactured by BASF, non-volatile content 100%), and 0.8 parts by mass of polytetrafluoroethylene (manufactured by Daikin Industries, Ltd., Polyflon PTFE D-210C, non-volatile content 60%), to obtain a comparative positive electrode composite slurry 1.
[0230] (Comparative positive electrode composite slurry 2) A comparative positive electrode composite slurry 2 was obtained by the same procedure as for the positive electrode composite slurry 1, except that the material ratios were changed to 16.5 parts by mass of the comparative dispersion composition 2, 0.3 parts by mass of carboxymethyl cellulose (manufactured by Daicel FineChem Corporation, #1190), 1.1 parts by mass of ion-exchanged water, 31.9 parts by mass of LFP (LFP-400 (manufactured by BASF, non-volatile content 100%), and 0.8 parts by mass of polytetrafluoroethylene (manufactured by Daikin Industries, Ltd., Polyflon PTFE D-210C, non-volatile content 60%).
[0231] (Positive electrode composite slurry 101) Capacity 150cm 3 Into the plastic container, 31.1 parts by mass of NMP solution in which 8% by mass of PVdF (polyvinylidene fluoride, Solvey, Solef#5130) was dissolved, and 0.4 parts by mass of NMP were weighed. Then, 24.9 parts by mass of dispersion composition 101 was added, and the mixture was stirred at 2000 rpm for 30 seconds using a rotation-revolution mixer (Awatori Rentaro, ARE-310). Then, 96.7 parts by mass of positive electrode active material NCM1 was added, and the mixture was stirred at 2000 rpm for 2.5 minutes using a rotation-revolution mixer (Awatori Rentaro, ARE-310), to obtain positive electrode composite slurry 101.
[0232] (Positive electrode composite material slurries 102 to 104, comparative positive electrode composite material slurries 101 to 102) Dispersion composition 101 was changed to dispersion compositions 102 to 104 and comparative dispersion compositions 101 to 102, and the same procedure as for positive electrode mixture slurry 101 was used to obtain positive electrode mixture slurries 102 to 104 and comparative positive electrode mixture slurries 101 to 102, respectively.
[0233] <6> Fabrication and evaluation of electrode films <6-1> Electrode film for negative electrode (Example 2-1: Negative electrode 1) The obtained negative electrode composite slurry 1 was applied to a copper foil having a thickness of 20 μm using an applicator, and the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a negative electrode (negative electrode 1). The weight per unit area of the composite layer was 10 mg / cm. 2 The density of the composite layer after rolling is 1.6 g / cm 3 It was.
[0234] (Examples 2-2 to 2-12: Negative electrodes 2 to 12) Negative electrode mixture slurry 1 was changed to negative electrode mixture slurry 2 to 12, and negative electrodes 2 to 12 were obtained in the same manner as for negative electrode 1.
[0235] (Comparative Examples 2-1 to 2-4: Comparative Negative Electrodes 1 to 4) The negative electrode mixture slurry 1 was changed to comparative negative electrode mixture slurries 1 to 4, and comparative negative electrodes 1 to 4 were obtained in the same manner as for negative electrode 1, respectively.
[0236] <6-2> Positive electrode film (Example 3-1: Positive electrode 1) The obtained positive electrode mixture slurry 1 was applied onto an aluminum foil having a thickness of 20 μm using an applicator, and then dried in an electric oven at 120° C.±5° C. for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3 ton hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 1). The weight per unit area of the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 2.1 g / cc.
[0237] (Examples 3-2 to 3-7, Comparative Examples 3-1 to 3-2: Positive Electrodes 2 to 7, Comparative Positive Electrodes 1 to 2) Positive electrode composite slurry 1 was changed to positive electrode composite slurry 2 to 7 and comparative positive electrode composite slurry 1 to 2, and positive electrodes 2 to 7 and comparative positive electrodes 1 to 2 were obtained in the same manner as for positive electrode 1, respectively.
[0238] (Examples 3-101 to 3-104, Comparative Examples 3-101 to 3-102: Positive Electrodes 101 to 104, Comparative Positive Electrodes 101 to 102) Positive electrode composite slurry 1 was changed to positive electrode composite slurry 101-104 and comparative positive electrode composite slurry 101-102, and positive electrodes 101-104 and comparative positive electrodes 101-102 were obtained in the same manner as for positive electrode 1, respectively.
[0239] <8> Laminated lithium-ion secondary battery (Example 4-1: Battery 1 for evaluating negative electrode) The negative electrode 1 and the standard positive electrode were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively. The punched negative electrode and standard positive electrode, together with a separator (porous polypropylene film) inserted between them, were inserted into an aluminum laminate bag and dried in an electric oven at 70°C for 1 hour. Next, a non-aqueous electrolyte was prepared in a glove box filled with argon gas. Specifically, first, a mixed solvent was prepared by mixing ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a ratio of 1:1:1 (volume ratio). Next, 1 part by mass each of VC (vinylene carbonate) and FEC (fluoroethylene carbonate) was added as additives to 100 parts by mass of the mixed solvent, and LiPF 6 A non-aqueous electrolyte solution was obtained by dissolving the above-mentioned compound at a concentration of 1 M. Next, 2 mL of the non-aqueous electrolyte solution was poured into the aluminum laminate bag, and the aluminum laminate was sealed to prepare a laminate-type lithium ion secondary battery (battery 1 for evaluating the negative electrode).
[0240] (Examples 4-2 to 4-12 and Comparative Examples 4-1 to 4-4) Laminated lithium ion secondary batteries (batteries for evaluating negative electrodes) 2 to 12 and comparative negative electrodes 1 to 4 were prepared in the same manner as in Example 4-1, except that the negative electrode 1 in Example 4-1 was changed to negative electrodes 2 to 12 and comparative negative electrodes 1 to 4.
[0241] (Examples 5-1 to 5-7, 5-101 to 5-104, and Comparative Examples 5-1 to 5-2, 5-101 to 5-102) The laminated lithium ion secondary batteries using the positive electrode and the standard negative electrode were prepared in the same manner as in Example 4-1, except that the negative electrode in Example 4-1 was changed to a standard negative electrode, and the positive electrode was changed to positive electrodes 1 to 7, positive electrodes 101 to 104, comparative positive electrodes 1 to 2, and comparative positive electrodes 101 to 102, to obtain positive electrode evaluation batteries 1 to 7, positive electrode evaluation batteries 101 to 104, comparative positive electrode evaluation batteries 1 to 2, and comparative positive electrode evaluation batteries 101 to 102, respectively.
[0242] The rate characteristics and cycle characteristics of the laminated lithium ion secondary battery were evaluated. The evaluation criteria are shown below. The evaluation results are shown in Tables 4 and 5.
[0243] (Method of evaluating rate characteristics of secondary batteries) The obtained secondary battery for negative electrode evaluation and secondary battery for positive electrode evaluation were placed in a thermostatic chamber at 25 ° C., and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current 1 mA (0.02 C)) was performed at a charge current of 10 mA (0.2 C) and a charge end voltage of 4.3 V, constant current discharging was performed at a discharge current of 10 mA (0.2 C) and a discharge end voltage of 3 V. After repeating this operation three times, constant current / constant voltage charging (cutoff current (1 mA 0.02 C)) was performed at a charge current of 10 mA (0.2 C) and a charge end voltage of 4.3 V, and constant current discharging was performed at discharge currents of 0.2 C and 3 C until the discharge end voltage reached 3.0 V, and the discharge capacity was calculated for each. The rate characteristic can be expressed by the ratio of the 0.2 C discharge capacity to the 3 C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity x 100 (%)
[0244] <Judgment criteria> ◎: Rate characteristics are 80% or more (excellent) ○: Rate characteristics are 70% or more and less than 80% (good) △: Rate characteristics are 60% or more but less than 70% (bad)
[0245] (Method of evaluating cycle characteristics of secondary batteries) The obtained secondary battery for negative electrode evaluation and secondary battery for positive electrode evaluation were placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (SM-8, manufactured by Hokuto Denko). After constant current / constant voltage charging (cutoff current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 200 times. The cycle characteristics can be expressed as the ratio of the 3rd 0.5C discharge capacity at 25°C to the 200th 0.5C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic = 200th 0.5C discharge capacity / 3rd 0.5C discharge capacity × 100 (%)
[0246] <Judgment criteria> ◎◎: 90% or more (best) ◎: 85% or more (excellent) ○: 80% or more but less than 85% (good) ×: Less than 80% (defective)
[0247] [Table 1]
[0248] [Table 2]
[0249] [Table 3]
[0250] [Table 4]
[0251] [Table 5]
[0252] As shown in the table, the examples in which the physical property values of the CNTs observed in the CNT dispersion composition fall within the specified ranges can provide secondary batteries that exhibit good rate characteristics and cycle characteristics.
[0253] For example, in Comparative Example 4-1, the linearity index of the CNT in the CNT dispersion composition is low, so it is expected that the number of active material particles that one CNT contacts in the secondary battery is small. In such a case, when the secondary battery is repeatedly charged and discharged, the ratio of the active material particles that are connected to each other by CNTs decreases due to the volume change of the active material, and the cycle characteristics are thought to deteriorate. In Comparative Example 4-2, the average outer diameter of the CNT in the CNT dispersion composition is large, so the conductivity of the CNT in the secondary battery is reduced, and the rate characteristics are thought to deteriorate. Similar trends were observed in Comparative Examples 5-1 and 5-2 and other Comparative Examples.
Claims
1. A carbon nanotube dispersion composition comprising carbon nanotubes, a dispersant, and a solvent, and satisfying the following (1) and (2): (1) The average outer diameter of carbon nanotubes contained in the carbon nanotube dispersion composition, calculated from an SEM image of the carbon nanotubes, is 15 nm or more and 50 nm or less. (2) When the target pixel group of an SEM image of carbon nanotubes contained in a carbon nanotube dispersion composition is defined as a carbon nanotube, and linearity is defined as the distance between the two most distant points (absolute maximum length) divided by the length of the free curve (skeleton length), the percentage of carbon nanotubes with a linearity of 0.9 or more for a skeleton length of 1 μm or more is 40% or more and 90% or less.
2. (3) In the Raman spectrum of the coating film of the carbon nanotube dispersion composition, -1 The maximum peak intensity in the range of G, 1310 to 1350 cm -1 2. The carbon nanotube dispersion composition according to claim 1, wherein the G / D ratio is 1.0 to 20.0, where D is the maximum peak intensity within the range.
3. (4) After freeze-drying the carbon nanotube dispersion composition, the powder passed through a 60 μm mesh has a BET specific surface area relative to the mass of carbon nanotubes of 50 to 130 m 2 The carbon nanotube dispersion composition according to claim 1, wherein the carbon nanotube dispersion composition has a molecular weight of 1000 or more.
4. (5) The carbon nanotube dispersion composition according to claim 1, wherein the complex modulus of elasticity at 25° C. and a frequency of 10 Hz as determined by dynamic viscoelasticity measurement is 4 Pa or more and 200 Pa or less.
5. (6) The carbon nanotube dispersion composition according to claim 1, which has a phase angle of 3° or more and 60° or less at 25° C. and a frequency of 10 Hz as measured by dynamic viscoelasticity measurement.
6. A carbon nanotube resin composition comprising the carbon nanotube dispersion composition according to claim 1 and a binder.
7. A composite slurry comprising the carbon nanotube dispersion composition according to claim 1 , a binder, and an active material.
8. 6. An electrode film, comprising a coating film of a composite slurry, the composite slurry comprising the carbon nanotube dispersion composition according to claim 1, a binder, and an active material.
9. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode comprises the electrode film according to claim 8.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP1992155776A
Nonaqueous electrolyte secondary battery
JP1992237971A
Negative electrode material and secondary battery using the same
JP2004178922A
Conductive material dispersion liquid, electrode paste, and conductive material coating active substance
JP2011070908A
Multilayer carbon nanotube aggregate and method for producing the same
JP2012082077A